Solid-state battery, solid-state battery preparation method, and preparation system
Patent Information
- Application Number
- CN202610758763.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-29
- Publication Date
- 2026-10-09
AI Technical Summary
然而,固态电池的规模化应用仍面临制造工艺上的核心挑战
[0059]这一协同机制使得最终制得的固态电池中,各功能层之间通过互渗区域实现了物理、化学与力学性能的完美匹配,在充放电过程中能够协同响应电极材料的体积变化,自适应地维持界面紧密接触,从而在降低外部拘束压力的条件下,依然能够保持低界面阻抗、高容量保持率与长循环寿命。
Smart Images

Figure CN122889808A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a solid-state battery, its preparation method and preparation system, belonging to the field of all-solid-state lithium-ion battery technology. Background Technology
[0002] With the increasing demands for battery energy density and safety in electric vehicles and large-scale energy storage, solid-state batteries, which use non-flammable solid electrolytes instead of traditional liquid electrolytes, are considered a key next-generation energy storage technology. In theory, solid-state batteries can fundamentally solve the safety hazards of liquid batteries and are compatible with high-energy-density lithium metal anodes, thus significantly improving overall battery performance. However, the large-scale application of solid-state batteries still faces core challenges in manufacturing processes.
[0003] Several key challenges exist in the fabrication of solid-state batteries: First, the solid electrolyte layer requires the formation of a uniform, dense, and controllable-thickness thin film on a large-area substrate. Traditional methods, such as dry pressing, struggle to achieve continuous fabrication of large-area films, while slurry coating methods are prone to generating pores and cracks during drying, affecting ion transport efficiency. Second, the electrode and solid electrolyte form a rigid solid-solid contact with a small interfacial area and high impedance. Furthermore, volume changes during charging and discharging easily lead to interfacial separation, causing rapid performance degradation. Additionally, the material systems and processing requirements of the positive electrode layer, electrolyte layer, and negative electrode layer differ. A process of independently preparing each layer before stacking is not only cumbersome and costly but also makes it difficult to guarantee interfacial compatibility and overall consistency between the multilayer structures.
[0004] To address these issues, thin film fabrication technology has attracted attention. However, existing thin film fabrication methods still have limitations when applied to solid-state batteries: films formed solely through deposition are typically in a particle-packed state with high intralayer porosity and discontinuous ion transport channels; interlayer bonding is weak during multilayer structure fabrication, making it difficult to effectively reduce interfacial impedance; and for solid electrolyte materials such as sulfides that are sensitive to air or polar solvents, the requirements for slurry preparation and process environment control are extremely stringent.
[0005] Therefore, how to achieve high-quality integrated fabrication of various functional layers in solid-state batteries, and fundamentally improve the solid-solid interface contact state and reduce interface impedance, has become a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0006] The primary technical problem to be solved by this invention is to provide a solid-state battery.
[0007] Another technical problem to be solved by the present invention is to provide a method for preparing the above-mentioned solid-state battery.
[0008] Another technical problem to be solved by the present invention is to provide a preparation system for the above-mentioned solid-state battery.
[0009] To achieve the above-mentioned technical objectives, the present invention adopts the following technical solution: According to a first aspect of the present invention, a solid-state battery is provided, comprising a current collector, a composite positive electrode layer, an electrolyte layer and a composite negative electrode layer arranged sequentially in a stacking direction; The solid-state battery further includes at least one interface buffer layer, which is disposed between the composite positive electrode layer and the electrolyte layer, and / or between the electrolyte layer and the composite negative electrode layer; At least one of the interface buffer layers extends into each other with at least one adjacent layer. The mutually extending portions constitute an interpenetrating region, and the thickness of the interpenetrating region along the stacking direction is 0.5μm-5μm.
[0010] In the solid-state battery provided by the present invention, the chemical composition of the material in the interpenetration region changes continuously and gradually along the stacking direction.
[0011] According to the solid-state battery provided by the present invention, at least one interface buffer layer includes a first interface buffer layer and a second interface buffer layer; the first interface buffer layer is disposed between the composite positive electrode layer and the electrolyte layer, and the second interface buffer layer is disposed between the electrolyte layer and the composite negative electrode layer.
[0012] According to the solid-state battery provided by the present invention, interpenetration regions are respectively formed between the first interface buffer layer and the composite positive electrode layer, between the first interface buffer layer and the electrolyte layer, between the second interface buffer layer and the electrolyte layer, and between the second interface buffer layer and the composite negative electrode layer.
[0013] According to the solid-state battery provided by the present invention, in the interpenetrating region, the porosity changes continuously and linearly along the thickness direction, without any abrupt changes in porosity.
[0014] According to the solid-state battery provided by the present invention, the porosity variation rate along the layer thickness direction in the interpenetrating region is ≤5% / μm.
[0015] According to the solid-state battery provided by the present invention, the average porosity P of the interpenetrating region satisfies the following relationship: in, The average porosity of the first functional layer corresponding to the interpenetrating region is the bulk average porosity. The average porosity of the second functional layer corresponding to the interpenetrating region is the average porosity of the central region of the functional layer away from the interpenetrating region.
[0016] According to a second aspect of the present invention, a method for preparing the above-described solid-state battery is provided, comprising the following steps: A composite positive electrode layer is formed on the current collector; An electrolyte layer, at least one interface buffer layer, and a composite negative electrode layer are formed on the side of the composite positive electrode layer away from the current collector, such that at least one of the interface buffer layers is located between the composite positive electrode layer and the electrolyte layer, and / or between the electrolyte layer and the composite negative electrode layer; After further processing, a solid-state battery is obtained; During the formation of at least one of the interface buffer layer, the electrolyte layer, and the composite negative electrode layer, an energy field is simultaneously applied to assist in the formation of the interface buffer layer and at least one adjacent layer, so that the at least one interface buffer layer extends into each other to form an interpenetrating region.
[0017] According to the solid-state battery fabrication method provided by the present invention, at least one interface buffer layer includes a first interface buffer layer and a second interface buffer layer; the step of forming an electrolyte layer, at least one interface buffer layer, and a composite negative electrode layer on the side of the composite positive electrode layer away from the current collector includes: The first interface buffer layer is formed on the composite positive electrode layer; The electrolyte layer is formed on the first interface buffer layer by spraying. The second interface buffer layer is formed on the electrolyte layer by spraying. The composite negative electrode layer is formed on the second interface buffer layer; Furthermore, an energy field is applied simultaneously during the formation of the first interface buffer layer, the electrolyte layer, the second interface buffer layer, and the composite negative electrode layer.
[0018] According to the solid-state battery fabrication method provided by the present invention, the energy field assistance includes at least one of low-intensity pulsed laser scanning, focused infrared radiation, or pulsed hot air assistance.
[0019] According to the solid-state battery fabrication method provided by the present invention, the energy field-assisted application parameter is: power density 0.1 W / mm². 2 Up to 1W / mm 2 The area of action moves synchronously with the area of spraying.
[0020] According to the solid-state battery preparation method provided by the present invention, when the energy field assistance includes focused infrared radiation, the wavelength of the focused infrared radiation is 2μm to 5μm, the diameter of the irradiated area is 1mm to 3mm, and the focused infrared radiation causes the surface of the irradiated particles to be instantly heated to 150°C to 200°C.
[0021] According to the solid-state battery fabrication method provided by the present invention, the step of forming a composite positive electrode layer on the current collector includes: A positive electrode active material, a first conductive agent, a first ionic conductor additive, and a binder are dispersed in a solvent to prepare a positive electrode slurry. The positive electrode slurry is deposited on the surface of the current collector by ultrasonic spraying. After spraying, it is dried in a vacuum environment at 80°C for 12 hours.
[0022] According to the solid-state battery preparation method provided by the present invention, in the positive electrode slurry, the mass ratio of positive electrode active material, first ion conductor additive, first conductive agent and binder is (60-90):(5-35):(1-5):(1-5).
[0023] According to the solid-state battery preparation method provided by the present invention, the positive electrode active material includes at least one of lithium cobalt oxide, nickel-cobalt-manganese ternary positive electrode, and sulfur composite positive electrode. The first ionic conductor additive includes at least one of the following: silver sulfide electrolyte, thio-LISICON type electrolyte, LGPS type electrolyte, glassy sulfide electrolyte, glass ceramic type electrolyte, or halogen-doped derivatives of any of the foregoing. The first conductive agent is any one or more of the following: particulate conductive agent, fibrous conductive agent, flake conductive agent, or a first composite conductive agent composed of at least two of the aforementioned conductive agents.
[0024] According to the solid-state battery preparation method provided by the present invention, the particulate conductive agent includes at least one of acetylene black, Ketjen black, Super P, and conductive carbon black.
[0025] According to the solid-state battery preparation method provided by the present invention, the fibrous conductive agent includes at least one of vapor-grown carbon fiber, single-walled carbon nanotube, multi-walled carbon nanotube, and carbon fiber.
[0026] According to the solid-state battery preparation method provided by the present invention, the sheet-like conductive agent includes at least one of graphene, conductive graphite, and expanded graphite.
[0027] According to the solid-state battery preparation method provided by the present invention, the first composite conductive agent includes at least one of a composite of carbon nanotubes and carbon black, a composite of graphene and carbon black, or a composite of carbon nanotubes and graphene.
[0028] According to the solid-state battery preparation method provided by the present invention, the solid content of the positive electrode slurry is 40% to 65%.
[0029] According to the solid-state battery preparation method provided by the present invention, the solid content of the positive electrode slurry is 50% to 55%.
[0030] According to the solid-state battery preparation method provided by the present invention, the step of forming the first interface buffer layer on the composite positive electrode layer includes: A polymer matrix and lithium salt are dissolved in a solvent to prepare an interface buffer layer slurry, which is then deposited onto the surface of the composite positive electrode layer using ultrasonic spraying.
[0031] According to the solid-state battery preparation method provided by the present invention, the step of forming the electrolyte layer on the first interface buffer layer by spraying includes: Solid electrolyte material and binder are dispersed in a solvent to form an electrolyte slurry, which is then deposited on the surface of the first interface buffer layer using ultrasonic spraying.
[0032] According to the solid-state battery preparation method provided by the present invention, the mass ratio of the solid electrolyte material to the binder is (90-99.9):(0.1-10).
[0033] According to the solid-state battery preparation method provided by the present invention, the solid electrolyte material includes at least one of sulfide solid electrolyte, oxide solid electrolyte, polymer solid electrolyte or halide solid electrolyte.
[0034] According to the solid-state battery preparation method provided by the present invention, the solid content of the electrolyte slurry is 40-70%.
[0035] According to the solid-state battery preparation method provided by the present invention, the step of forming the second interface buffer layer on the electrolyte layer by spraying includes: A polymer matrix and lithium salt are dissolved in a solvent to prepare an interface buffer layer slurry, which is then deposited onto the surface of the electrolyte layer using ultrasonic spraying.
[0036] According to the solid-state battery preparation method provided by the present invention, the polymer matrix includes at least one of polyvinylidene fluoride-hexafluoropropylene, polyoxyethylene, or polypropylene carbonate.
[0037] According to the solid-state battery preparation method provided by the present invention, the lithium salt includes at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium bis(pentafluoroethylsulfonyl)imide, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium perchlorate, lithium bis(oxalateborate), lithium difluorooxalateborate, lithium tetrafluorooxalate phosphate, and lithium trifluoromethanesulfonate.
[0038] According to the solid-state battery preparation method provided by the present invention, the amount of lithium salt added is 0.1-5% of the total mass of the interface buffer layer slurry.
[0039] According to the solid-state battery preparation method provided by the present invention, the step of forming the composite negative electrode layer on the second interface buffer layer includes: A negative electrode slurry is prepared by dispersing the negative electrode active material, the second conductive agent, the second ionic conductor additive and the binder in a solvent. The negative electrode slurry is deposited on the surface of the second interface buffer layer by ultrasonic spraying, and an energy field is applied simultaneously during the process of spraying to form the composite negative electrode layer.
[0040] According to the solid-state battery preparation method provided by the present invention, in the negative electrode slurry, the mass ratio of negative electrode active material, second ion conductor additive, second conductive agent and binder is (60-85):(10-30):(1-5):(1-5).
[0041] According to the solid-state battery preparation method provided by the present invention, the negative electrode active material is any one or more of the following materials: silicon, silicon-carbon composite material, silicon suboxide, graphite, lithium metal, tin, aluminum, antimony, titanium dioxide, lithium titanate, or a composite material formed from at least two of the aforementioned materials. The second ion conductor additive includes at least one of the following: sulfide solid electrolyte, oxide solid electrolyte, halide solid electrolyte, polymer solid electrolyte, and composite solid electrolyte; The second conductive agent is any one or more of the following: carbon black conductive agent, carbon fiber conductive agent, carbon sheet conductive agent, metal conductive agent, or a second composite conductive agent composed of at least two of the aforementioned conductive agents.
[0042] According to the solid-state battery preparation method provided by the present invention, when an energy field is simultaneously applied during the spraying process to form the composite negative electrode layer, the energy field assistance used is a low-intensity pulsed laser scan. The wavelength of the low-intensity pulsed laser scan is 800-1200 nm, the pulse width is 10 ns-100 ms, and the energy density is 0.1-10 J / cm³. 2 .
[0043] According to the solid-state battery preparation method provided by the present invention, the binder is any one or more of the following: polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid, polyisobutylene, styrene-ethylene-butene-styrene block copolymer, polyamide-imide, polyvinyl alcohol, polyethylene oxide, or a composite binder composed of at least two of the foregoing.
[0044] According to the solid-state battery preparation method provided by the present invention, the solvent includes at least one selected from N-methylpyrrolidone, acetone, n-heptane, acetonitrile, tetrahydrofuran, toluene, xylene, isobutyl isobutyrate, or cyclohexane.
[0045] According to the solid-state battery preparation method provided by the present invention, when forming each layer by ultrasonic spraying, the spraying parameters are as follows: atomization frequency of 20kHz to 200kHz, carrier gas pressure of 0.1MPa to 0.5MPa, spraying rate of 1mL / min to 100mL / min, substrate temperature of the current collector of 25℃ to 120℃, and spraying distance of 5cm to 30cm.
[0046] According to the solid-state battery preparation method provided by the present invention, the solid-state battery obtained after subsequent processing includes: The resulting multilayer structure is vacuum dried at 60-120℃ for 6-24 hours, then rolled under 20-80MPa pressure, and then punched, stacked, and packaged to obtain a solid-state battery.
[0047] According to the solid-state battery preparation method provided by the present invention, the thickness of the composite positive electrode layer and the composite negative electrode layer is 20 μm to 500 μm, the thickness of the electrolyte layer is 5 μm to 100 μm, and the thickness of the first interface buffer layer and the second interface buffer layer are each independently 0.1 μm to 10 μm.
[0048] According to a third aspect of the present invention, a system for fabricating the above-described solid-state battery is provided, the system comprising: At least four independently controlled ultrasonic atomizing nozzles, each of which is used to atomize and spray the slurry onto the surface of the current collector or the surface of the layer structure already formed on the current collector; The slurry delivery unit is connected to each of the ultrasonic atomizing nozzles and is used to supply slurry to each of the ultrasonic atomizing nozzles. An energy field auxiliary generator, the area of which moves synchronously with the spraying area of the ultrasonic atomizing nozzle, is used to apply an energy field during the spraying process; A temperature-controlled moving platform is used to carry and heat the collector fluid, and to move the collector fluid relative to the ultrasonic atomizing nozzle; and The computer program control system is electrically connected to the ultrasonic atomizing nozzle, the slurry delivery unit, the energy field auxiliary generator, and the temperature-controlled moving platform, and is used to control the spraying path, spraying parameters, energy field parameters, and platform temperature and moving speed.
[0049] The core principle of this invention lies in combining multi-layer ultrasonic spraying with synchronous energy field assistance to achieve the transformation of each functional layer of solid-state battery from "particle stacking" to "in-situ fusion", thereby fundamentally solving the problems of poor solid-solid interface contact and obstructed ion transport within the layers.
[0050] Specifically, ultrasonic spraying atomizes the slurry of each functional layer into micron-sized uniform droplets, forming a wet film structure with uniformly distributed particles during the deposition process.
[0051] During the formation of at least one of the electrolyte layer and at least one interface buffer layer, an energy field, such as focused infrared radiation, low-intensity pulsed laser, or pulsed hot air, is simultaneously applied. This energy field precisely targets the newly deposited wet film region, instantly heating the surface of the solid electrolyte particles or the polymer matrix in the interface buffer layer to its softening temperature range. During this process, the particle surface softens locally under the influence of the energy field, and surface atoms or molecular chains gain sufficient migration capacity. Driven by surface tension and capillary forces, adjacent particles fuse and necking occur, while the solvent rapidly evaporates. This transforms the original wet film, in its particle-packed state, into a dense structure with fused particles and extremely low porosity. This in-situ densification mechanism avoids the shrinkage stress and porosity defects caused by solvent evaporation during traditional drying processes, creating continuous and interconnected ion transport channels within the electrolyte layer, significantly improving ionic conductivity.
[0052] In an embodiment where an interface buffer layer is provided between the electrolyte layer and the composite negative electrode layer, during the formation of the composite negative electrode layer, a low-intensity pulsed laser is simultaneously applied to scan the newly deposited negative electrode region. The laser energy instantly activates the surface of the negative electrode active particles, introducing active sites on the particle surface and enhancing the interfacial physical contact and chemical bonding force between the composite negative electrode layer and the interface buffer layer. At the same time, the local thermal effect of the laser can promote the rapid evaporation of the solvent in the negative electrode slurry, avoiding the negative impact of solvent residue on the electrochemical activity of the negative electrode. This mechanism enables the high-capacity silicon-carbon negative electrode to form a tight and stable interfacial bond with the solid electrolyte layer, effectively suppressing the interfacial separation problem caused by the volume expansion of silicon particles during charging and discharging.
[0053] Meanwhile, the energy field-assisted mechanism at the interlayer interface is even more crucial. The introduction of an energy field is a key strategy for achieving tight interlayer contact and uniform stress distribution. Unlike the passive contact relying on mechanical pressure in traditional multilayer stacking processes, the energy field-assisted method can actively regulate interface evolution behavior during electrolyte layer formation, significantly improving interlayer bonding quality. During the formation of the electrolyte layer, at least one interface buffer layer, and / or composite negative electrode layer, the synchronously applied energy field can act not only on the currently deposited functional layer itself but also on the interface buffer layer or electrode layer adjacent to it. This causes particle intercalation, molecular chain interpenetration, and component interperfusion at the adjacent layer interfaces, forming a three-dimensional interlocking network similar to an "anchoring" structure and an interperfusion region without obvious physical boundaries. In one embodiment with a first interface buffer layer, the thermal effect of the energy field can act on the first interface buffer layer and its adjacent composite positive electrode layer and electrolyte layer, forming interpenetration regions between the first interface buffer layer and the composite positive electrode layer, and between the first interface buffer layer and the electrolyte layer. In one embodiment with a second interface buffer layer, the thermal effect of the energy field can act on the second interface buffer layer and its adjacent electrolyte layer and composite negative electrode layer, forming interpenetration regions between the second interface buffer layer and the electrolyte layer, and between the second interface buffer layer and the composite negative electrode layer. The interpenetration region described in this invention refers to a transition region without a clear physical interface formed between two adjacent functional layers through component interpenetration, molecular chain interpenetration, and particle interembedding assisted by an energy field. Within this transition region, the chemical composition and elastic modulus of the material exhibit a continuous and gradual change along the layer thickness direction, rather than the abrupt change of traditional stacking processes, thereby eliminating stress concentration caused by interlayer modulus mismatch, reducing interfacial impedance, and improving interlayer bonding.
[0054] Within the interpenetrating region layer, when the interpenetrating region is formed between the interface buffer layer and the electrolyte layer, the material composition can gradually transition from polymer-dominated in the interface buffer layer to inorganic solid electrolyte particle-dominated in the electrolyte layer. When the interpenetrating region is formed between the interface buffer layer and an adjacent composite positive or negative electrode layer, the material composition can continuously transition between the polymer / lithium salt system of the interface buffer layer and the composite system of active materials, conductive agents, ionic conductor additives, and binders in the adjacent electrode layer. Thus, the elastic modulus at the interface exhibits a continuous gradual change rather than an abrupt change, eliminating the interfacial stress concentration caused by modulus mismatch in traditional multilayer stacked structures. In summary, energy field assistance not only achieves densification of the electrolyte layer itself but also fundamentally solves the mechanical failure problem caused by interfacial modulus mismatch in multilayer solid electrolyte structures. By constructing an interpenetrating region with continuous modulus, gradual composition, and interlocking structure, uniform stress distribution is achieved throughout the interlayer range, avoiding local stress concentration, and ultimately obtaining an interlayer interface with high mechanical reliability, low interfacial impedance, and excellent electrochemical stability.
[0055] In embodiments where a second interface buffer layer is simultaneously provided, during the formation of the second interface buffer layer and / or the composite negative electrode layer, the energy field applied simultaneously causes the formation of interpenetration regions with continuously varying composition and modulus between the second interface buffer layer and the electrolyte layer, and between the second interface buffer layer and the composite negative electrode layer.
[0056] The construction of this multi-layered interpenetrating region creates a continuous ion transport path with progressively changing impedance between the composite positive electrode layer and the composite negative electrode layer, fundamentally eliminating the problems of high interfacial impedance and easy separation during cycling caused by rigid solid-solid contact.
[0057] On the negative electrode side, the activation effect of the pulsed laser and the stress buffering function of the second interface buffer layer work together to enhance the interfacial bonding force and provide buffer space for the volume expansion of the silicon-carbon negative electrode, further ensuring the structural stability of the interface during cycling.
[0058] From a system perspective, the technical solution of this invention realizes a paradigm shift in solid-state battery fabrication from "layer-by-layer stacking" to "integrated construction." Ultrasonic spraying technology ensures precise controllability of the thickness of each layer and large-area uniformity, providing a technological foundation for the continuous fabrication of multi-layer structures. Synchronous energy field assistance combines the originally independent "deposition" and "densification" steps into one, completing the internal densification of each layer and its fusion optimization with the lower layer interface at the same time as the formation of each layer. For the negative electrode layer, the interfacial bonding is enhanced through a surface activation mechanism, avoiding secondary interfacial damage and residual stress caused by separate layer-by-layer fabrication and subsequent hot pressing in traditional processes.
[0059] This synergistic mechanism enables the functional layers in the final solid-state battery to achieve a perfect match of physical, chemical and mechanical properties through interpenetration regions. During charging and discharging, it can synergistically respond to the volume changes of the electrode materials and adaptively maintain tight interfacial contact. Thus, even with reduced external confinement pressure, it can still maintain low interfacial impedance, high capacity retention and long cycle life.
[0060] Compared with existing technologies, this invention combines multi-layer ultrasonic spraying with synchronous energy field assistance to construct an integrated solid-state battery fabrication process from the composite positive electrode layer to the composite negative electrode layer. During the formation of at least one of the electrolyte layer and at least one interface buffer layer, the synchronous application of an energy field assists in situ softening and fusing of the sprayed particles or polymer matrix. This transforms the particle-stacking film layer, which is difficult to avoid in traditional processes, into a dense structure with high density and low porosity, effectively solving the problem of discontinuous ion transport channels within the solid electrolyte layer.
[0061] Simultaneously, the energy field-assisted thermal effect causes molecular chain interpenetration and component interpermeation at the interlayer interfaces, thereby forming interpermeable regions with continuously varying compositions and moduli between at least one interface buffer layer and the electrolyte layer, and / or between at least one interface buffer layer and an adjacent composite positive or negative electrode layer. In a preferred embodiment where both a first and a second interface buffer layer are simultaneously provided, interpermeable regions with continuously varying compositions and moduli can be formed between the first interface buffer layer and the composite positive electrode layer, between the first interface buffer layer and the electrolyte layer, between the second interface buffer layer and the electrolyte layer, and between the second interface buffer layer and the composite negative electrode layer, respectively. This interpermeable region eliminates rigid contact and modulus abrupt changes between multilayer structures, significantly reduces interfacial contact impedance, and fundamentally improves the core problem of poor solid-solid interface contact and easy separation during cycling in solid-state batteries.
[0062] Simultaneous application of low-intensity pulsed laser during the formation of the composite anode layer activates the surface of silicon-carbon particles, significantly enhancing the interfacial bonding between the composite anode layer and the second interface buffer layer. This effectively suppresses interfacial separation and capacity decay of the high-capacity silicon-carbon anode due to volume expansion during charge and discharge. This synergistic improvement in performance allows the solid-state battery fabricated in this invention to operate stably under lower confinement pressure conditions, exhibiting high energy density, excellent rate performance, and long cycle life.
[0063] The preparation method provided by this invention achieves significant technical improvements in electrochemical performance. Test results from examples show that the solid-state battery prepared using this method exhibits approximately 60% lower interfacial impedance between the cathode and electrolyte compared to traditional coating and stacking processes, an approximately 4 percentage point improvement in initial coulombic efficiency, and a capacity retention rate of over 94% after 200 cycles at 0.5C.
[0064] Furthermore, this invention integrates the complex steps of traditional solid-state battery fabrication, which involve independent preparation and subsequent stacking and pressing, into a single continuous spraying and molding process from current collector to complete battery. This avoids alignment deviations, interface contamination, and solvent interleaving issues during interlayer transfer, greatly simplifying the process and reducing manufacturing costs. Ultrasonic spraying technology itself offers advantages such as high material utilization, large-area film formation, and precise thickness control. Combined with energy field-assisted synchronous densification and interface optimization, it achieves high-performance solid-state battery fabrication while also considering the feasibility and economy of large-scale production, providing a practical technical path for the industrial application of solid-state batteries. Attached Figure Description
[0065] Figure 1 This is a flowchart of a solid-state battery fabrication method in some embodiments of the present invention; Figure 2 These are schematic diagrams of the solid-state battery structure in some embodiments of the present invention; Figure 3 These are cross-sectional views of a solid-state battery in some embodiments of the present invention; Figure 4 These are cycle performance diagrams of solid-state batteries in some embodiments of the present invention. Detailed Implementation
[0066] The technical content of the present invention will now be described in detail with reference to the accompanying drawings and specific embodiments.
[0067] The technical concept in this invention is to simultaneously apply an energy field during the formation of at least one of the electrolyte layer and at least one interface buffer layer, causing adjacent functional layers to fuse at the interface and form an interpenetrating region. Therefore, unlike the prior art which pursues clear boundaries between layers and avoids interpenetration, this invention actively constructs a gradual fusion between layers to eliminate the problems of high impedance and easy separation caused by rigid interface contact.
[0068] See Figure 1 This invention provides a method for preparing a solid-state battery. In summary, the method includes: forming a composite positive electrode layer on a current collector; forming an electrolyte layer, at least one interface buffer layer, and a composite negative electrode layer on the side of the composite positive electrode layer away from the current collector, such that at least one of the interface buffer layers is located between the composite positive electrode layer and the electrolyte layer, and / or between the electrolyte layer and the composite negative electrode layer; and obtaining a solid-state battery after subsequent processing.
[0069] In some embodiments, the interface buffer layer includes a first interface buffer layer and a second interface buffer layer. In a preferred embodiment where both a first interface buffer layer and a second interface buffer layer are simultaneously provided, the method includes steps S1 to S6: S1. A composite positive electrode layer is formed on the current collector.
[0070] The pre-prepared composite cathode slurry is uniformly loaded onto at least one surface of the current collector through a suitable deposition process. After drying and shaping, a composite cathode layer with uniform structure and stable composition is formed. This composite cathode layer can provide a continuous electron conduction path and an efficient lithium-ion migration channel, effectively avoiding problems such as interlayer delamination and poor interface contact that occur during the preparation of multilayer structures, thus laying the foundation for the stable performance of the overall electrochemical performance of solid-state batteries.
[0071] In some embodiments, in order to obtain a composite cathode slurry with uniform dispersion and rheological properties adapted to the deposition process, the cathode active material, the first ion conductor additive, the first conductive agent and the binder are first added to a suitable solvent according to a preset mass ratio, and stirred and mixed under an inert atmosphere to form a uniform dispersion system without obvious agglomeration of each component in the solvent, thus completing the preparation of the composite cathode slurry.
[0072] In some embodiments, mixing can be performed using mixing equipment such as planetary mixers, high-speed shear dispersers, ball mills, homogenizers, etc.
[0073] In some embodiments, in order to balance the energy density, ion conduction efficiency and electronic conduction performance of the composite positive electrode layer, the mass ratio of positive electrode active material, first ion conductor additive, first conductive agent and binder in the composite positive electrode slurry is set to (60-90):(5-35):(1-5):(1-5). For example, the mass ratio of positive electrode active material, first ion conductor additive, first conductive agent and binder can be 80:15:2.5:2.5, 60:5:1:1 or 90:35:5:5, etc. The positive electrode active material is selected from at least one of lithium cobalt oxide, nickel-cobalt-manganese ternary cathode, and sulfur composite cathode. The first ionic conductor additive is selected from at least one of the following: silver sulfide electrolyte, thio-LISICON type electrolyte, LGPS type electrolyte, glassy sulfide electrolyte, glass ceramic type electrolyte, or halogen-doped derivatives of any of the above. The first conductive agent is any one or more of the following: granular conductive agent, fibrous conductive agent, flake conductive agent, or a first composite conductive agent composed of at least two of the aforementioned conductive agents; The adhesive is selected from at least one of polystyrene-ethylene-butene-polystyrene (SEBS), hydrogenated styrene-isoprene-styrene block copolymer (SEPS), styrene-butene-styrene block copolymer (SBS), styrene-isoprene-styrene block copolymer (SIS), styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), and polyisobutylene (PIB).
[0074] In some embodiments, in order to adapt the composite cathode slurry to the deposition requirements of the ultrasonic spraying process, and at the same time ensure the controllable evaporation of solvent and the uniformity of film structure during film formation, the solid content of the composite cathode slurry is controlled to be 40% to 65%; for example, the solid content of the composite cathode slurry is 42%, 44%, 46%, 48%, 50%, 52%, 54%, 56%, 58%, 60%, 62%, 64%, etc.
[0075] Preferably, the solid content of the composite cathode slurry is 50% to 55%.
[0076] The solvent used is selected from at least one of N-methylpyrrolidone, acetone, n-heptane, acetonitrile, tetrahydrofuran, toluene, xylene, isobutyl isobutyrate, and cyclohexane; In some embodiments, an ultrasonic spraying process is used to deposit a composite positive electrode slurry onto the surface of the current collector. During the spraying process, the current collector is fixed on a heated moving platform, and the slurry is uniformly covered on the surface of the current collector by controlling the movement path of the ultrasonic spraying nozzle. Multiple reciprocating sprays are used to achieve the preset thickness of the composite positive electrode layer. The platform temperature is controlled between 25°C and 120°C during the spraying process to promote rapid and synchronous evaporation of the solvent in the slurry during deposition, avoiding defects such as pinholes and cracks in the film layer caused by wet film sagging or solvent residue.
[0077] In some embodiments, the parameters of the ultrasonic spraying process are set to an atomization frequency of 20kHz to 200kHz, a carrier gas pressure of 0.1MPa to 0.5MPa, a spraying rate of 1mL / min to 100mL / min, and a spraying distance between the nozzle and the current collector controlled at 5cm to 30cm. Through the coordinated control of the above parameters, the slurry is ultrasonically atomized to form droplets with uniform particle size, ensuring the uniformity of the thickness and density of the deposited film layer, and avoiding problems such as local over-thickness or uneven thickness that affect subsequent interface bonding.
[0078] In some embodiments, after the composite cathode slurry is sprayed and deposited onto the current collector (forming a wet film on the current collector), the current collector is then dried in a vacuum environment at 80°C for 12 hours to thoroughly remove residual solvent from the wet film. This avoids the porosity and structural shrinkage caused by rapid solvent evaporation during atmospheric pressure drying. Therefore, the dried composite cathode layer forms a stable porous conductive network, providing a good physical anchoring point for the penetration and bonding of subsequent interface buffer layers, further enhancing interlayer bonding.
[0079] In some embodiments, the thickness of the composite cathode layer is controlled within the range of 20 μm to 500 μm, which can be flexibly adjusted according to the battery capacity design and electrochemical performance requirements. By precisely controlling the thickness, the energy density and rate performance requirements of the battery are matched, while ensuring the structural stability of the composite cathode layer during charging and discharging, and mitigating the structural collapse problem caused by changes in the volume of the active material.
[0080] S2. A first interface buffer layer is formed on the composite positive electrode layer.
[0081] Step S2 involves uniformly loading the pre-prepared interface buffer layer slurry onto the surface of the previously prepared composite cathode layer using a suitable deposition process. After drying and shaping, a continuous and uniform first interface buffer layer is formed. This first interface buffer layer can fill the micropores and uneven structures on the surface of the composite cathode layer, achieving a smooth transition in composition and structure between the composite cathode layer and the subsequent electrolyte layer. This effectively alleviates the problem of poor interface contact caused by rigid solid-solid contact, reduces the interface impedance between the cathode and the electrolyte, and isolates the direct contact between the cathode active material and the solid electrolyte, suppressing the interface side reactions between the two during charging and discharging. This provides a flat and stable interface foundation for the densification of the subsequent electrolyte layer, ensuring the interlayer bonding force and interface stability between the multilayer structures.
[0082] In some embodiments, in order to obtain an interface buffer layer slurry with excellent film-forming performance and good interface compatibility, the polymer matrix and lithium salt are first added to a suitable solvent, and stirred at a constant temperature in a closed environment until completely dissolved to form a uniform and clear polymer electrolyte solution, thus completing the preparation of the first interface buffer layer slurry. This slurry can achieve good wetting and spreading on the surface of the composite positive electrode layer, avoiding defects such as film discontinuity and pinholes caused by insufficient wettability of the slurry.
[0083] In some embodiments, to balance the lithium-ion conductivity, viscoelasticity, and interfacial stability of the first interface buffer layer, the polymer matrix is selected from at least one of polyvinylidene fluoride-hexafluoropropylene, polyoxyethylene, and polypropylene carbonate. The lithium salt includes at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium bis(pentafluoroethylsulfonyl)imide, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium perchlorate, lithium bis(oxalateborate), lithium difluorooxalateborate, lithium tetrafluorooxalate phosphate, and lithium trifluoromethanesulfonate. The amount of lithium salt added is 0.1-5% of the total mass of the interface buffer layer slurry. Through this formulation design, the formed first interface buffer layer can have a suitable lithium-ion conductivity while maintaining good viscoelasticity. During charging and discharging, it can adapt to the volume change of the electrode material and undergo adaptive deformation, avoiding interface separation.
[0084] In some embodiments, the solvent used to prepare the first interface buffer layer slurry is selected from at least one of N-methylpyrrolidone, acetone, n-heptane, acetonitrile, tetrahydrofuran, toluene, xylene, isobutyl isobutyrate, and cyclohexane. The amount of solvent is adjusted according to the target viscosity of the slurry so that the rheological properties of the slurry are adapted to the atomization requirements of the ultrasonic spraying process, ensuring the uniformity of droplets and the consistency of deposition during the spraying process.
[0085] In some embodiments, an ultrasonic spraying process is used to deposit a first interface buffer layer slurry onto the surface of the composite positive electrode layer. During the spraying process, the temperature of the substrate carrying the composite positive electrode layer and the current collector is controlled between 25°C and 120°C. The movement path of the ultrasonic spraying nozzle is controlled by programming so that the slurry is uniformly covered in the entire active area of the composite positive electrode layer. After multiple reciprocating sprayings, the first interface buffer layer reaches the preset target thickness.
[0086] In some embodiments, the parameters of the ultrasonic spraying process are set to an atomization frequency of 20kHz to 200kHz, a carrier gas pressure of 0.1MPa to 0.5MPa, a spraying rate of 1mL / min to 100mL / min, and a spraying distance between the nozzle and the composite positive electrode layer controlled at 5cm to 30cm. Through the coordinated control of the above parameters, the slurry is ultrasonically atomized to form droplets with uniform particle size, ensuring the uniformity of the thickness and the smoothness of the surface of the deposited film, and providing a stable interface basis for the subsequent preparation of the electrolyte layer.
[0087] In some embodiments, the thickness of the first interface buffer layer is controlled within the range of 0.1 μm to 10 μm. Through precise control of the thickness, the effects of interface transition, stress buffering and side reaction suppression are achieved, while avoiding the increase of the overall impedance of the battery due to an excessively thick interface buffer layer, thus ensuring the rate performance and energy density of the battery.
[0088] In some embodiments, the first interface buffer layer adopts a polymer matrix and lithium salt system, which can form a slight interfusion transition at the interface with the electrolyte layer during the subsequent electrolyte layer spraying and energy field assisted treatment, thereby constructing an interpenetration region between the composite cathode layer and the electrolyte layer, further reducing the interface contact resistance, and improving the interlayer bonding force to avoid the problem of interlayer delamination during battery cycling.
[0089] S3. An electrolyte layer is formed on the first interface buffer layer by spraying.
[0090] Step S3 involves uniformly depositing the pre-prepared electrolyte slurry onto the surface of the previously prepared first interface buffer layer using an ultrasonic spraying process. Throughout the spraying deposition process, an energy field is simultaneously applied to assist in the localization and fusion of the sprayed particles, promoting the densification of the electrolyte layer. Simultaneously, the electrolyte layer and the first interface buffer layer extend into each other, forming interpenetrating regions where components are mutually compatible. After drying and setting, a high-density, structurally complete electrolyte layer with continuous ion transport channels is formed. This electrolyte layer, as the core ion transport medium of the battery, can construct a stable and efficient lithium-ion migration path between the positive and negative electrodes, while isolating electron conduction between them, preventing internal short circuits. The combination of the densified structure and interpenetrating regions achieved with synchronous energy field assistance effectively reduces the overall interface impedance of the battery, improving its rate performance and cycle stability.
[0091] In some embodiments, in order to obtain an electrolyte slurry with uniform dispersion, excellent atomization performance, and suitability for ultrasonic spraying, the solid electrolyte material and binder are first added to a suitable anhydrous solvent, and then thoroughly mixed by high-speed shear dispersion under the protection of an inert atmosphere, so that the solid electrolyte particles are uniformly dispersed in the solvent, forming a suspension slurry system with no obvious agglomeration and stable solid content, thus completing the preparation of the electrolyte slurry. The protection of the inert atmosphere can avoid side reactions of solid electrolyte materials such as sulfides that are sensitive to air and moisture, and ensure that the intrinsic ion conduction performance of the electrolyte material is not damaged.
[0092] In some embodiments, the solid electrolyte material used in the electrolyte slurry is selected from at least one of sulfide solid electrolytes, oxide solid electrolytes, polymer solid electrolytes, and halide solid electrolytes.
[0093] In some embodiments, the adhesive used is selected from at least one of polystyrene-ethylene-butene-polystyrene (SEBS), hydrogenated styrene-isoprene-styrene block copolymer (SEPS), styrene-butene-styrene block copolymer (SBS), styrene-isoprene-styrene block copolymer (SIS), styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), and polyisobutylene (PIB).
[0094] In some embodiments, the mass ratio of solid electrolyte material to binder is (90-99.9):(0.1-10), such as 90:0.1, 99.9:10, etc., so as to ensure the structural stability of the electrolyte membrane layer while minimizing the negative impact of the binder on the overall ionic conductivity of the electrolyte layer.
[0095] In some embodiments, in order to adapt to the atomization requirements of ultrasonic spraying process and ensure the density of the electrolyte layer after deposition, the solid content of the electrolyte slurry is controlled to be 40-70%, for example, 45%, 50%, 55%, 60% or 65%, etc. The solvent used is selected from at least one of N-methylpyrrolidone, acetone, n-heptane, acetonitrile, tetrahydrofuran, toluene, xylene, isobutyl isobutyrate, and cyclohexane. The selection and amount of solvent can adjust the viscosity and rheological properties of the slurry, so that the slurry forms droplets with uniform particle size after ultrasonic atomization, avoiding problems such as poor atomization due to excessive viscosity or droplet splashing and uneven film formation due to excessively low viscosity.
[0096] In some embodiments, when depositing the electrolyte layer using ultrasonic spraying, the temperature of the substrate carrying the first interface buffer layer, the composite positive electrode layer, and the current collector is controlled between 25°C and 120°C. The ultrasonic spraying parameters are set to an atomization frequency of 20kHz to 200kHz, a carrier gas pressure of 0.1MPa to 0.5MPa, a spraying rate of 1mL / min to 100mL / min, and a spraying distance between the nozzle and the first interface buffer layer controlled between 5cm and 30cm. By programming to control the movement path of the nozzle and the number of reciprocating sprays, the electrolyte slurry is uniformly covered on the entire surface of the first interface buffer layer, gradually building an electrolyte wet film of a preset thickness.
[0097] In some embodiments, during the formation of at least one of the first interface buffer layer, the electrolyte layer, and the second interface buffer layer, an energy field linked to the spray nozzle is simultaneously applied to assist in forming at least one of the interface buffer layers and at least one adjacent layer into each other, thereby forming an interpenetrating region with continuously varying composition and modulus.
[0098] In some embodiments, an energy field is applied simultaneously during the formation of the first interface buffer layer, the electrolyte layer, and the second interface buffer layer.
[0099] In some embodiments, the energy field assistance is selected from at least one of low-intensity pulsed laser scanning, focused infrared radiation, and pulsed hot air assistance, and the power density of the energy field assistance is controlled at 0.1 W / mm². 2 Up to 1W / mm 2 Between these two processes, the area of action moves synchronously with the deposition area of the spray nozzle, thereby precisely irradiating the wet film area that has just been deposited on the substrate surface. This achieves localized instantaneous heating and softening of the sprayed particles, promotes the mutual fusion between particles and the rapid and controllable evaporation of the solvent, eliminates the internal pores formed by particle accumulation, realizes in-situ densification of the electrolyte layer, and promotes the formation of interpenetrating regions with mutually fused components between adjacent layers, further reducing interlayer contact resistance.
[0100] In some embodiments, when focused infrared radiation is selected as the energy field assist method, the wavelength of the infrared radiation is controlled between 2μm and 5μm, and the diameter of the irradiated area is controlled between 1mm and 3mm. Through the precise focusing of infrared energy, the surface of the irradiated solid electrolyte particles is instantly heated to 150°C to 200°C. This temperature range is lower than the decomposition temperature of the solid electrolyte material, which can achieve the softening and fusion of the particle surface without damaging the intrinsic properties of the electrolyte material, while avoiding damage to the structure of the bottom first interface buffer layer caused by high temperature.
[0101] In some embodiments, the thickness of the prepared electrolyte layer is controlled within the range of 5 μm to 100 μm. Through precise control of the thickness, while ensuring the mechanical strength and resistance to lithium dendrite penetration of the electrolyte layer, the transport path of lithium ions is shortened to the maximum extent, the battery's body impedance is reduced, and the battery's energy density, rate performance and safety performance are balanced.
[0102] In some embodiments, the material system of the electrolyte layer is compatible with the first interface buffer layer and the subsequently prepared second interface buffer layer. During the subsequent spraying and energy field-assisted treatment of the second interface buffer layer, a mutually permeable region with mutually compatible components is also formed between the electrolyte layer and the second interface buffer layer. This allows for the construction of a continuous multilayer structure with progressively changing impedance between the composite positive electrode layer and the composite negative electrode layer, avoiding impedance abrupt changes between the multilayer structures and ensuring the stability and efficiency of lithium-ion transport during the charging and discharging process of the battery.
[0103] S4. A second interface buffer layer is formed on the electrolyte layer by spraying.
[0104] Step S4 involves uniformly depositing the pre-prepared second interface buffer layer slurry onto the surface of the previously prepared electrolyte layer using an ultrasonic spraying process. An energy field is simultaneously applied throughout the spraying and deposition process to promote interfacial fusion between the second interface buffer layer and the electrolyte layer, forming a smoothly transitioning interpenetrating region. After drying and setting, a continuous, uniform, and highly viscoelastic second interface buffer layer is formed. This second interface buffer layer can fill microscopic defects on the electrolyte layer surface, achieving a smooth transition in structure and modulus between the electrolyte layer and the subsequent composite negative electrode layer. It effectively alleviates interfacial stress concentration caused by volume changes in the negative electrode active material during charging and discharging, preventing interfacial separation and microcrack formation. Simultaneously, it isolates the negative electrode active material from direct contact with the solid electrolyte, inhibiting interfacial side reactions and lithium dendrite growth. This provides a smooth, stable, and highly adhesive interfacial foundation for the subsequent composite negative electrode layer preparation, further reducing the overall interfacial impedance of the battery and improving its cycle stability and safety performance.
[0105] In some embodiments, the raw material selection, proportioning and preparation method of the second interface buffer layer slurry are completely consistent with those of the first interface buffer layer slurry, thereby ensuring the performance matching of the interface buffer layers on both sides inside the battery, while simplifying the preparation process and reducing the difficulty of process control.
[0106] In some embodiments, during the entire process of spraying and depositing the second interface buffer layer slurry, an energy field assisting the spray nozzle is applied simultaneously. The type and parameter range of the energy field assisting are completely consistent with the energy field assisting used in the preparation of the electrolyte layer. This promotes the interfusion of components between the second interface buffer layer and the bottom electrolyte layer without damaging the intrinsic properties of each layer material, forming a continuous and smooth interpenetrating region. At the same time, it achieves uniform densification of the second interface buffer layer, avoids defects such as film pores and cracks generated during solvent evaporation, and further enhances the interlayer bonding force between the second interface buffer layer and the electrolyte layer.
[0107] In some embodiments, the thickness of the second interface buffer layer is controlled within the range of 0.1 μm to 10 μm. Through precise control of the thickness, stress buffering, interface transition and side reaction suppression effects are achieved, while avoiding the increase of the overall impedance of the battery due to an excessively thick interface buffer layer, thus ensuring the rate performance and energy density of the battery.
[0108] In some embodiments, the second interface buffer layer adopts a polymer matrix and lithium salt system adapted to the first interface buffer layer and electrolyte layer, which can form a stable interpenetration region with the electrolyte layer and has good interfacial compatibility with the subsequently prepared composite negative electrode layer. In this way, a full gradient interface structure from the composite positive electrode layer to the composite negative electrode layer is constructed inside the battery, eliminating modulus abrupt changes and impedance abrupt changes between multilayer structures, maintaining tight interfacial contact during long-term charge and discharge cycles of the battery, effectively suppressing the growth of interfacial impedance, and improving the long cycle life of the battery.
[0109] S5. A composite negative electrode layer is formed on the second interface buffer layer; Step S5 involves uniformly loading the pre-prepared composite negative electrode slurry onto the surface of the previously prepared second interface buffer layer using a suitable deposition process. After drying and shaping, a structurally stable and uniformly composed composite negative electrode layer is formed. This composite negative electrode layer can provide stable lithium-ion insertion / extraction active sites for the battery charging and discharging process. At the same time, it forms a good interfacial bond with the underlying second interface buffer layer, synergistically adapting to the volume deformation of the negative electrode active material during charging and discharging, alleviating interfacial stress concentration, and avoiding interfacial separation and microcrack generation. The continuous electron conduction network and ion conduction channels constructed inside can ensure the efficient migration of lithium ions and the rapid transport of electrons, matching the electrochemical performance on the positive electrode side, and providing core support for the realization of high-rate performance and long cycle life of the battery.
[0110] In some embodiments, in order to obtain a composite negative electrode slurry with uniform dispersion and rheological properties adapted to the deposition process, the negative electrode active material, the second conductive agent, the second ionic conductor additive and the binder are weighed according to a preset mass ratio. The above solid materials are added to a suitable solvent and thoroughly mixed by planetary stirring, high-speed shear dispersion or ball milling process, so that each solid component forms a uniform dispersion system without obvious agglomeration in the solvent, thus completing the preparation of the composite negative electrode slurry.
[0111] In some embodiments, in order to balance the specific capacity, structural stability and ion-electron conduction efficiency of the composite negative electrode layer, the mass ratio of negative electrode active material, second ion conductor additive, second conductive agent and binder in the composite negative electrode slurry is set to (60-85):(10-30):(1-5):(1-5), for example 65:30:2.5:2.5, 60:10:1:1, 85:30:5:5, etc. The negative electrode active material is any one or more of the following materials: silicon, silicon-carbon composite material, silicon suboxide, graphite, lithium metal, tin, aluminum, antimony, titanium dioxide, lithium titanate, or a composite material formed from at least two of the aforementioned materials. The second ion conductor additive is selected from at least one of sulfide solid electrolytes, oxide solid electrolytes, halide solid electrolytes, polymer solid electrolytes, and composite solid electrolytes; The second conductive agent is any one or more of the following: carbon black conductive agent, carbon fiber conductive agent, carbon sheet conductive agent, metal conductive agent, or a second composite conductive agent composed of at least two of the aforementioned conductive agents; The adhesive is any one or more of the following: polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid, polyisobutylene, styrene-ethylene-butene-styrene block copolymer, polyamide-imide, polyvinyl alcohol, polyethylene oxide, or a composite adhesive composed of at least two of the foregoing. This ensures the material compatibility between the composite negative electrode layer and the preceding and following functional layers, while achieving a balance between high specific capacity and structural stability during cycling.
[0112] In some embodiments, the solvent used in the composite negative electrode slurry is selected from at least one of N-methylpyrrolidone, acetone, n-heptane, acetonitrile, tetrahydrofuran, toluene, xylene, isobutyl isobutyrate, and cyclohexane. The amount of binder added to the composite negative electrode slurry is controlled within the range of 0.1wt% to 0.5wt% to adjust the viscosity of the slurry and the mechanical properties after film formation, thereby ensuring the stability of the film structure and reducing the negative impact of the binder on the electrochemical activity of the negative electrode.
[0113] In some embodiments, an ultrasonic spraying process is used to deposit a composite negative electrode slurry onto the surface of the second interface buffer layer. During the spraying process, the temperature of the substrate supporting the multilayer structure is controlled between 25°C and 120°C. By controlling the movement path of the ultrasonic spraying nozzle, the slurry is uniformly covered on the entire active area of the second interface buffer layer. After multiple reciprocating sprayings, the composite negative electrode layer reaches the preset thickness. Temperature control of the substrate during the spraying process can promote the synchronous evaporation of the solvent in the slurry during the deposition process, avoiding defects such as pinholes and cracks in the film layer caused by wet film sagging or solvent residue.
[0114] In some embodiments, the ultrasonic spraying parameters used for the composite negative electrode layer are consistent with those for the composite positive electrode layer, set to an atomization frequency of 20kHz to 200kHz, a carrier gas pressure of 0.1MPa to 0.5MPa, a spraying rate of 1mL / min to 100mL / min, and a spraying distance between the nozzle and the second interface buffer layer controlled at 5cm to 30cm.
[0115] In some embodiments, an energy field is simultaneously applied throughout the entire spray deposition process. This energy field is a low-intensity pulsed laser scan with a wavelength of 800-1200 nm, a pulse width of 10 ns-100 ms, and an energy density of 0.1-10 J / cm². 2 By simultaneously scanning the newly deposited negative electrode area with a low-intensity pulsed laser, the surface of the negative electrode active particles can be slightly activated, enhancing the physical contact and interfacial bonding between the composite negative electrode layer and the second interface buffer layer, thus avoiding the problem of interlayer delamination during battery cycling.
[0116] In some embodiments, the thickness of the composite negative electrode layer is controlled within the range of 20 μm to 500 μm, which can be flexibly adjusted according to the capacity design and electrochemical performance requirements of the battery. Through precise control of the thickness, the energy density and rate performance requirements of the battery are matched, while ensuring that the composite negative electrode layer can cooperate with the second interface buffer layer to adapt to volume deformation during charging and discharging, and maintain the tightness of the interface contact.
[0117] In some embodiments, an interpenetrating region with continuously varying composition and modulus can be formed between the composite negative electrode layer and the second interface buffer layer, thereby eliminating abrupt changes in modulus and impedance at the negative electrode interface. During long-term charge-discharge cycles, this maintains the high efficiency and stability of interfacial ion transport, effectively suppressing the continuous increase in interfacial impedance. Simultaneously, in conjunction with the stress buffering effect of the second interface buffer layer, it alleviates interface failure problems caused by negative electrode volume expansion, improving the battery's long-cycle stability and safety performance.
[0118] S6. After further processing, a solid-state battery is obtained.
[0119] In this preferred embodiment, the integrated multilayer structure of current collector-composite positive electrode layer-first interface buffer layer-electrolyte layer-second interface buffer layer-composite negative electrode layer prepared by the aforementioned multilayer ultrasonic spraying process is subjected to subsequent processing including vacuum drying, roll densification, punching, stacking, and sealing. This process thoroughly removes residual solvents from the multilayer structure, further optimizes the density and interlayer bonding of each functional layer, completes the regularization and isolation protection of the cell, and ultimately obtains a solid-state battery with a complete structure, tight interface bonding, and stable electrochemical performance. This subsequent processing flow is highly compatible with the aforementioned integrated spraying preparation process, which can maximize the preservation of the structural advantages of the interpenetrating regions between each layer, and avoid problems such as interface misalignment, poor contact, and interlayer delamination caused by traditional step-by-step preparation and multilayer stacking processes. This ensures that the final solid-state battery has both high energy density, excellent rate performance, and long cycle stability.
[0120] In some embodiments, after the coating of all functional layers is completed, the resulting integrated multilayer structure is first placed in a vacuum drying environment for deep drying treatment. The drying temperature is controlled at 60-120°C and the drying time is controlled at 6-24 hours. The constant temperature vacuum drying thoroughly removes the trace amounts of residual solvent in each layer structure, avoiding problems such as interfacial side reactions and swelling during battery cycling caused by solvent residue. At the same time, the drying process further promotes the molecular chain entanglement and structural fusion at the interface of each layer, consolidating the bonding stability of the interpenetrating region.
[0121] In some embodiments, after vacuum drying, a roller press is used to cold-press and densify the multilayer structure. The roller pressing pressure is controlled at 20-80 MPa. The gentle cold pressing process further improves the internal density of the composite positive electrode layer, electrolyte layer, and composite negative electrode layer, optimizes the contact state between active particles, conductive agents, and ion conductors, and constructs a more continuous and stable electron and ion transport channel. At the same time, it further enhances the interfacial bonding force between functional layers, eliminates micro-gaps between layers, and further reduces the bulk impedance and interfacial impedance of the battery. Moreover, this pressure parameter can avoid the damage to the interpenetration region structure caused by high-pressure roller pressing, and fully preserve the technical effect of the in-situ interface modification of the present invention.
[0122] In some embodiments, after the roll densification process is completed, the multilayer electrode sheets are transferred to a glove box protected by an inert atmosphere and punched according to the preset battery specifications and dimensions to obtain battery cell electrode sheets with regular shape and uniform size. Then, according to the battery's design capacity and output voltage requirements, the punched electrode sheets are matched and stacked with the corresponding current collectors. During the stacking process, the alignment accuracy of each functional layer is strictly controlled to avoid problems such as internal short circuits, capacity decay, and shortened cycle life caused by electrode misalignment, so as to prepare a battery cell body with regular structure and uniform performance for subsequent packaging.
[0123] In some embodiments, after the stacking operation is completed, an appropriate bonding pressure is applied to the cell body, and then, according to the application scenario and specification requirements of the battery, the cell body is installed in a button battery case or a soft-pack battery aluminum-plastic film case. The entire process is completed in an inert atmosphere to seal and encapsulate, ultimately producing a solid-state battery cell. During the encapsulation process, the moisture and oxygen content in the environment are strictly controlled to avoid side reactions of water- and oxygen-sensitive solid electrolyte materials such as sulfides and electrode active materials, so as to preserve the intrinsic electrochemical performance of the battery materials to the greatest extent and ensure the long-term stability and safety of the battery.
[0124] In the final solid-state battery, the thickness of the composite positive electrode layer and the composite negative electrode layer is controlled within the range of 20 μm to 500 μm, the thickness of the electrolyte layer is controlled within the range of 5 μm to 100 μm, and the thickness of the first interface buffer layer and the second interface buffer layer are each independently controlled within the range of 0.1 μm to 10 μm. Stable interpenetration regions are formed between the first interface buffer layer and the composite positive electrode layer, between the first interface buffer layer and the electrolyte layer, between the second interface buffer layer and the electrolyte layer, and between the second interface buffer layer and the composite negative electrode layer inside the battery. This structure can effectively eliminate modulus abrupt changes and impedance abrupt changes between multilayer structures, maintain the tightness of interface contact during charging and discharging, adapt to the volume deformation of electrode materials, and ultimately achieve excellent cycle stability and rate performance of the battery.
[0125] The present invention also provides a solid-state battery prepared by the aforementioned method. The solid-state battery includes a current collector, a composite positive electrode layer, an electrolyte layer, a composite negative electrode layer, and at least one interface buffer layer; at least one of the interface buffer layers is disposed between the composite positive electrode layer and the electrolyte layer, and / or between the electrolyte layer and the composite negative electrode layer.
[0126] See Figure 2 and Figure 3 In a preferred embodiment where a first interface buffer layer and a second interface buffer layer are simultaneously provided, the solid-state battery is an integrated layered stacked structure, which includes a current collector, a composite positive electrode layer, a first interface buffer layer, an electrolyte layer, a second interface buffer layer and a composite negative electrode layer from bottom to top. The functional layers are tightly bonded together, with no obvious interlayer delamination or void defects.
[0127] Interpenetrating regions are formed at at least one of the following interfaces: between at least one of the interface buffer layers and the electrolyte layer; between at least one of the interface buffer layers and an adjacent composite positive electrode layer or composite negative electrode layer; the thickness of the interpenetrating region is 0.5μm-5μm, for example 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, etc., and within the interpenetrating region, the chemical composition and elastic modulus of the material change continuously and gradually along the thickness direction.
[0128] In a preferred embodiment where a first interface buffer layer and a second interface buffer layer are simultaneously provided, at least one of the following locations is formed: between the first interface buffer layer and the composite positive electrode layer, between the first interface buffer layer and the electrolyte layer, between the second interface buffer layer and the electrolyte layer, and between the second interface buffer layer and the composite negative electrode layer; within the interpenetration region, the chemical composition and elastic modulus of the material gradually change along the layer thickness direction. This interpenetration region can fundamentally improve the core problems of poor interface contact, high impedance, and easy interface separation during cycling caused by rigid solid-solid contact in solid-state batteries, significantly improving the rate performance, cycle stability, and safety of solid-state batteries.
[0129] In some embodiments, interpenetration regions are formed between the first interface buffer layer and the composite positive electrode layer, between the first interface buffer layer and the electrolyte layer, between the second interface buffer layer and the electrolyte layer, and between the second interface buffer layer and the composite negative electrode layer.
[0130] In some embodiments, the porosity within the interpenetrating region exhibits a continuous linear gradient along the layer thickness direction, without abrupt changes in porosity. This structural feature means that the volume fraction of micropores within the material does not jump or drop abruptly at a narrow interface from the interface buffer layer side to the electrolyte layer side, but rather transitions smoothly and gradually. This continuous gradient in porosity is consistent with the continuous gradient in chemical composition and elastic modulus in the interface region, together constituting the intrinsic properties of the interpenetrating region. The continuously gradient porosity feature effectively avoids the local stress concentration problem caused by abrupt changes in porosity in traditional multilayer stacked structures, resulting in a more uniform mechanical response at the interface during charging and discharging, and significantly reducing the risk of microcrack initiation and propagation. Simultaneously, the smooth transition in porosity means that the tortuosity of the ion transport channels also gradually changes within the interface region. This helps maintain the stability of lithium-ion migration flux across different functional layers, avoiding ion transport bottlenecks caused by abrupt changes in pore structure, thereby further reducing interface impedance and improving the structural reliability and electrochemical stability of solid-state batteries during long-cycle operation.
[0131] In some embodiments, the degree of porosity variation within the interpenetrating region is quantitatively controlled, meaning that the rate of porosity variation along the thickness direction within the interpenetrating region is ≤5% / μm. The physical meaning of this feature is that, across the entire thickness of the interpenetrating region, the porosity increment at any micrometer scale is constrained to an extremely narrow range, thereby ensuring the gradual change characteristics of the interfacial region's microstructure. This limitation on the porosity variation rate, along with the continuous gradual change in chemical composition and elastic modulus in the interfacial region, forms an inherent harmony and unity, and these three factors together determine the stability of the interpenetrating region in terms of mechanical and electrochemical behavior.
[0132] In some embodiments, the average porosity P of the interpenetrating region satisfies the following relationship: in, The average porosity of the first functional layer corresponding to the interpenetrating region is the bulk average porosity. The average porosity of the second functional layer corresponding to the interpenetrating region is the average porosity of the central region of the functional layer away from the interface.
[0133] In some embodiments, the current collector is selected from a high electron conductivity substrate adapted to the positive electrode system. The surface of the current collector can be roughened or pre-coated with a conductive carbon layer according to the application requirements, thereby improving the interfacial bonding force between the current collector and the composite positive electrode layer, reducing the contact resistance between the current collector and the active layer, preventing the composite positive electrode layer from peeling off from the surface of the current collector during long-term battery cycling, and ensuring the structural stability of the battery throughout its entire life cycle.
[0134] In some embodiments, a composite positive electrode layer is disposed on at least one surface of the current collector. It is a composite porous conductive structure comprising a positive electrode active material, a first ion conductor additive, a first conductive agent, and a binder, capable of simultaneously providing a continuous electron conduction path and an efficient lithium-ion migration channel. The thickness of the composite positive electrode layer is controlled within the range of 20 μm to 500 μm, and can be flexibly adjusted according to the battery capacity design and electrochemical performance requirements, ensuring battery energy density while also considering bidirectional lithium-ion and electron conduction efficiency.
[0135] In some embodiments, the first interface buffer layer is closely attached to the surface of the composite positive electrode layer away from the current collector. It is a gel-state or composite electrolyte structure containing a polymer matrix and lithium salt. Its own modulus is lower than that of the electrolyte layer. It can fully fill the micro-unevenness and pores on the surface of the composite positive electrode layer, so as to achieve a smooth transition in structure and performance between the composite positive electrode layer and the electrolyte layer.
[0136] The thickness of the first interface buffer layer is controlled within the range of 0.1μm to 10μm. This can isolate the direct contact between the positive electrode active material and the electrolyte layer without significantly increasing the overall impedance of the battery, suppress the interface side reactions during charging and discharging, adapt to the volume changes of the electrode material, alleviate interface stress concentration, and avoid interface separation problems during cycling.
[0137] In some embodiments, the electrolyte layer is disposed on the surface of the first interface buffer layer away from the composite positive electrode layer. It serves as the core ion transport medium of the battery and is prepared using an ultrasonic spraying process combined with in-situ energy field-assisted densification. This results in high intralayer density, absence of significant porosity and penetrating cracks, enabling the construction of a continuous and stable lithium-ion transport channel between the positive and negative electrodes, while completely isolating electron conduction between them to prevent internal short circuits. The thickness is controlled within the range of 5μm to 100μm, ensuring mechanical strength and resistance to lithium dendrite penetration while minimizing the lithium-ion transport path, reducing the battery's bulk impedance, and balancing energy density and safety performance.
[0138] In some embodiments, the second interface buffer layer is closely attached to the side of the electrolyte layer away from the first interface buffer layer. Its raw material system, structural characteristics and thickness range are consistent with the first interface buffer layer. It is a gel-state or composite electrolyte structure containing a polymer matrix and lithium salt. Its own modulus is lower than that of the electrolyte layer. It can fully fill the micro-defects on the surface of the electrolyte layer and realize a smooth transition in structure and modulus between the electrolyte layer and the composite negative electrode layer.
[0139] This second interface buffer layer can fully adapt to the large volume deformation of the negative electrode active material during charging and discharging, alleviate interface stress concentration, avoid interface separation and microcrack generation, and at the same time isolate the direct contact between the negative electrode active material and the electrolyte layer, suppress interface side reactions and lithium dendrite growth, and provide a flat, stable interface foundation with excellent bonding for the composite negative electrode layer.
[0140] In some embodiments, the composite negative electrode layer is disposed on the surface of the second interface buffer layer away from the electrolyte layer. It is a composite conductive structure containing a negative electrode active material, a second conductive agent, a second ion conductor additive and a binder, which can provide stable lithium ion intercalation and deintercalation active sites for the battery charging and discharging process and form a precise match with the electrochemical performance of the composite positive electrode layer.
[0141] The thickness of the composite negative electrode layer is controlled within the range of 20μm to 500μm, which can be flexibly adjusted according to the battery capacity design and the matching requirements of positive and negative electrode capacity, ensuring the structural stability and reversibility of lithium ion insertion and extraction during the battery charging and discharging process.
[0142] In some embodiments, the interpenetrating regions formed between the first interface buffer layer and the composite positive electrode layer, between the first interface buffer layer and the electrolyte layer, between the second interface buffer layer and the electrolyte layer, and between the second interface buffer layer and the composite negative electrode layer are interface structures with continuously changing composition and modulus formed through in-situ energy field-assisted treatment, rather than rigid abrupt interfaces formed by multi-layer stacking in traditional processes. Within the interpenetrating region, the material components of adjacent layers permeate and fuse in situ, forming a smooth transition structure without obvious interface boundaries. Simultaneously, the modulus of the interface region gradually changes from the active layer to the electrolyte layer, avoiding the interface stress concentration problem caused by abrupt modulus changes. This interpenetrating region can significantly reduce the interfacial contact impedance between adjacent functional layers, improve interlayer bonding, and continuously maintain the tightness of the interface contact during long-term charge-discharge cycles. It adapts to the volume expansion and contraction of electrode materials, avoiding problems such as interface separation and microcrack propagation, effectively suppressing the continuous increase of interface impedance during cycling, and fundamentally improving the cycle stability and rate performance of solid-state batteries.
[0143] In some embodiments, the solid-state battery is prepared by an integrated multilayer ultrasonic spraying process combined with in-situ interface modification. Compared with traditional step-by-step preparation and stacking assembly of solid-state batteries, the alignment accuracy between functional layers is higher, the interface bonding is tighter, and there are no preparation defects such as interlayer misalignment and voids. It can operate stably under low constraint pressure and has high energy density, excellent rate performance and long cycle life. It is suitable for multiple application scenarios such as new energy vehicle power batteries, large-scale energy storage power stations and consumer electronics.
[0144] The present invention also provides a solid-state battery fabrication system for implementing the above-described fabrication method. The system includes at least four independently controlled ultrasonic atomizing nozzles, each used to atomize and spray slurry onto the surface of the current collector or the surface of a layered structure already formed on the current collector. The system also includes a slurry delivery unit connected to each ultrasonic atomizing nozzle for supplying slurry to each nozzle. Furthermore, the system includes an energy field auxiliary generator whose operating area moves synchronously with the spraying area of the ultrasonic atomizing nozzle to apply an energy field during the spraying process. The system also includes a temperature-controlled moving platform for carrying and heating the current collector and moving it relative to the ultrasonic atomizing nozzles. Finally, the system includes a computer program control system electrically connected to the ultrasonic atomizing nozzles, the slurry delivery unit, the energy field auxiliary generator, and the temperature-controlled moving platform for controlling the spraying path, spraying parameters, energy field parameters, and platform temperature and movement speed.
[0145] The above system enables the automated and precise implementation of the solid-state battery integrated multilayer spraying preparation process described in this invention.
[0146] Example 1
[0147] This embodiment describes the fabrication of a solid-state battery based on a nickel-cobalt-manganese ternary cathode (LiNi0.8Co0.1Mn0.1O2, NCM811), a silver-germanium sulfide electrolyte (Li6PS5Cl, LPSC), and a silicon-carbon anode. The specific steps are as follows: 1. Slurry preparation Preparation of composite cathode slurry: NCM811 powder, LPSC powder, a first conductive agent composed of vapor-grown carbon fiber and acetylene black, and polyvinylidene fluoride binder are mixed in a mass ratio of 80:15:2.5:2.5. N-methylpyrrolidone solvent is added and the mixture is stirred evenly by planetary stirring in an inert atmosphere glove box to form a homogeneous slurry with a solid content of about 60%.
[0148] Preparation of the interface buffer layer slurry: Polyvinylidene fluoride-hexafluoropropylene polymer was dissolved in acetone, and lithium bis(trifluoromethanesulfonyl)imide (3% by weight of the total slurry) was added. The mixture was stirred until completely dissolved to form a clear polymer electrolyte solution.
[0149] Preparation of electrolyte slurry: LPSC sulfide electrolyte powder with a particle size D50 of 1 μm was dispersed in anhydrous n-heptane, and polyisobutylene accounting for 1% of the total mass of the slurry was added as a binder. The mixture was dispersed at high speed under argon protection to form a stable suspension with a solid content of about 40%.
[0150] Preparation of composite negative electrode slurry: Nano-silicon-carbon composite material (SiOx / C, D50=5μm), LPSC, conductive agent VGCF, and polyvinylidene fluoride PVDF binder are mixed in a mass ratio of 65:30:2.5:2.5, xylene solvent is added, and the mixture is stirred into a homogeneous slurry.
[0151] 2. Formation of the composite cathode layer A four-channel computer-controlled ultrasonic spraying system, equipped with a heated moving platform and a nozzle frequency of 120kHz, was used. The aluminum foil current collector was fixed on the 60℃ heated platform, and the composite positive electrode slurry was sprayed through the ultrasonic nozzle. The spraying parameters were: carrier gas pressure 0.3MPa, spraying rate 20mL / min, nozzle scanning speed 100mm / s, and spraying distance 15cm. Multiple reciprocating sprays were used to achieve a positive electrode layer thickness of approximately 80μm. After spraying, the material was initially dried in an 80℃ vacuum oven for 12 hours.
[0152] 3. Formation of multilayer solid electrolyte layers First, switch to the nozzle for loading the interface buffer layer slurry and spray the interface buffer layer slurry onto the dried composite cathode layer surface. The spraying parameters are: carrier gas pressure 0.2MPa, spraying rate 5mL / min, and platform temperature 40℃, forming a uniform polymer film with a thickness of about 3μm, which is the first interface buffer layer.
[0153] Subsequently, the process was switched to the nozzle loaded with the electrolyte slurry, and the focusing infrared heater, which moved synchronously with the nozzle, was activated. Simultaneously, infrared irradiation was focused onto the newly deposited wet film area while the electrolyte slurry was being sprayed. The spraying parameters were: carrier gas pressure 0.25 MPa, spraying rate 10 mL / min, platform temperature 80℃, and infrared power density 1 W / mm². 2 The infrared wavelength range is 2μm to 5μm, and the irradiated area has a diameter of approximately 2mm. The infrared energy instantly heats the surface of the LPSC particles to 150℃ to 200℃, softening the particles and causing them to fuse together, while the solvent evaporates rapidly. Through multiple sprayings, an electrolyte layer with a thickness of approximately 20μm is constructed.
[0154] Finally, switch to the nozzle that loads the interface buffer layer slurry, and spray the interface buffer layer slurry again on the surface of the electrolyte layer to form a second interface buffer layer.
[0155] 4. Formation of the composite negative electrode layer The platform temperature was lowered to 50℃, and the nozzle loaded with composite negative electrode slurry was switched on. The composite negative electrode slurry was sprayed onto the surface of the multilayer solid electrolyte layer. The spraying parameters were: carrier gas pressure 0.3MPa, spraying rate 15mL / min. During the spraying process, a low-intensity pulsed laser was simultaneously used to scan the newly deposited negative electrode area. The laser wavelength was 1064nm, the pulse width was 10ns, and the energy density was 0.1J / cm². 2 The coating thickness of the negative electrode layer is approximately 50 μm.
[0156] 5. Post-processing The multi-layered electrode sheet with the above-mentioned coating was vacuum dried at 120°C for 24 hours to remove residual solvent. It was then cold-pressed at 50 MPa using a roller press. Finally, in an inert atmosphere glove box, the resulting structure was punched to the required size, stacked with the current collector, and then packaged in a coin cell or pouch cell case under pressure to obtain a solid-state battery cell.
[0157] Comparative Example 1 Composite positive electrode film, electrolyte film and composite negative electrode film were prepared by traditional scraping method, and the interface buffer layer was prepared on the surface of the corresponding electrode film by scraping method. No energy field assistance was applied during the preparation process; the film was formed solely by vacuum drying at 80°C for 12 hours. After the prepared films are stacked in sequence, they are cold-pressed under a pressure of 50 MPa. The remaining post-processing steps are exactly the same as in Example 1, and a solid-state battery is assembled.
[0158] Example 2
[0159] This embodiment provides a solid-state battery fabrication method based on lithium-rich manganese-based material Li1.2Ni0.13Co0.13Mn0.54O2, lithium lanthanum zirconium tantalum oxide-polyethylene oxide (LLZTO-PEO) composite electrolyte, and silicon-carbon anode. The specific steps are as follows: 1. Slurry preparation Preparation of composite cathode slurry: Li1.2Ni0.13Co0.13Mn0.54O2 powder, LLZTO-PEO powder, a first conductive agent composed of vapor-grown carbon fiber and acetylene black, and polyvinylidene fluoride binder are mixed in a mass ratio of 80:15:2.5:2.5. N-methylpyrrolidone solvent is added and the mixture is stirred evenly by planetary stirring in an inert atmosphere glove box to form a homogeneous slurry with a solid content of about 60%.
[0160] Preparation of the interface buffer layer slurry: Polyvinylidene fluoride-hexafluoropropylene polymer was dissolved in acetone, and lithium bis(trifluoromethanesulfonyl)imide (2% by weight of the total slurry) was added. The mixture was stirred until completely dissolved to form a clear polymer electrolyte solution.
[0161] Preparation of electrolyte slurry: LLZTO-PEO electrolyte powder with a particle size D50 of 1 μm was dispersed in acetonitrile, and polyisobutylene accounting for 1% of the total mass of the slurry was added as a binder.
[0162] Preparation of composite negative electrode slurry: The composite negative electrode active material composed of nano-silicon-carbon composite material (SiOx / C, D50=5μm) and graphite, LLZTO-PEO composite solid electrolyte, conductive agent VGCF, and polyvinylidene fluoride PVDF binder are mixed in a mass ratio of 65:30:2.5:2.5, N-methylpyrrolidone solvent is added, and the mixture is stirred into a homogeneous slurry.
[0163] 2. Formation of the composite cathode layer A four-channel computer-controlled ultrasonic spraying system, equipped with a heated moving platform and a nozzle frequency of 120kHz, was used. The aluminum foil current collector was fixed on the 60℃ heated platform, and the composite positive electrode slurry was sprayed through the ultrasonic nozzle. The spraying parameters were: carrier gas pressure 0.3MPa, spraying rate 20mL / min, nozzle scanning speed 100mm / s, and spraying distance 15cm. Multiple reciprocating sprays were used to achieve a positive electrode layer thickness of approximately 80μm. After spraying, the material was initially dried in an 80℃ vacuum oven for 12 hours.
[0164] 3. Formation of multilayer solid electrolyte layers First, switch to the nozzle for loading the interface buffer layer slurry and spray the interface buffer layer slurry onto the dried composite cathode layer surface. The spraying parameters are: carrier gas pressure 0.2MPa, spraying rate 5mL / min, and platform temperature 40℃, forming a uniform polymer film with a thickness of about 3μm, which is the first interface buffer layer.
[0165] Subsequently, the nozzle was switched to the one loaded with electrolyte slurry, and a pulsed hot air assist mechanism was activated, moving synchronously with the nozzle. Simultaneously with the spraying of the electrolyte slurry, the instantaneous high-temperature airflow promoted localized melting of PEO and network interweaving of LLZTO nanowires, achieving densification. The spraying parameters were: carrier gas pressure 0.25 MPa, spraying rate 10 mL / min, and platform temperature 80 °C. Through multiple sprays, a dense composite electrolyte layer with a thickness of approximately 20 μm was constructed.
[0166] Finally, switch to the nozzle that loads the interface buffer layer slurry, and spray the interface buffer layer slurry again on the surface of the electrolyte layer to form a second interface buffer layer.
[0167] 4. Formation of the composite negative electrode layer The platform temperature was lowered to 50℃, and the nozzle loaded with composite negative electrode slurry was switched on. The composite negative electrode slurry was sprayed onto the surface of the multilayer solid electrolyte layer. The spraying parameters were: carrier gas pressure 0.3MPa, spraying rate 15mL / min. During the spraying process, a low-intensity pulsed laser was simultaneously used to scan the newly deposited negative electrode area. The laser wavelength was 1064nm, the pulse width was 10ns, and the energy density was 0.1J / cm². 2 The coating thickness of the negative electrode layer is approximately 50 μm.
[0168] 5. Post-processing The multi-layered electrode sheet with the above-mentioned coating was vacuum dried at 120°C for 24 hours to remove residual solvent. It was then cold-pressed at 50 MPa using a roller press. Finally, in an inert atmosphere glove box, the resulting structure was punched to the required size, stacked with the current collector, and then packaged in a coin cell or pouch cell case under pressure to obtain a solid-state battery cell.
[0169] Comparative Example 2 Composite positive electrode film, electrolyte film and composite negative electrode film were prepared by traditional scraping method, and the interface buffer layer was prepared on the surface of the corresponding electrode film by scraping method. No energy field assistance was applied during the preparation process; the film was formed solely by vacuum drying at 80°C for 12 hours. After the prepared films are stacked in sequence, they are cold-pressed under a pressure of 50 MPa. The remaining post-processing steps are exactly the same as in Example 2, and a solid-state battery is assembled.
[0170] Example 3
[0171] The difference between this embodiment and Embodiment 1 is that the number of electrolyte layer sprayings is reduced, forming a thin electrolyte layer with a thickness of about 10 μm. The remaining steps are the same as in Embodiment 1.
[0172] Example 4
[0173] The difference between this embodiment and Embodiment 1 is that the number of electrolyte layer sprayings is increased to form an electrolyte layer with a thickness of about 40 μm. The remaining steps are the same as in Embodiment 1.
[0174] Example 5
[0175] The difference between this embodiment and Embodiment 1 is that, during the spraying of the electrolyte slurry, the energy field assistance applied synchronously is pulsed hot air instead of infrared laser. Specific parameters are: hot air temperature 180-220℃, pulse frequency 2 Hz, pulse width 0.5 s, airflow 5 L / min, and nozzle-to-substrate distance 3 cm. The thickness of the first and second interface buffer layers is 2 μm. The remaining steps are the same as in Embodiment 1.
[0176] Example 6
[0177] The difference between this embodiment and Embodiment 1 is that, during the spraying of the electrolyte slurry, the energy field assistance applied simultaneously is infrared lamp irradiation, rather than focused infrared laser. Specific parameters: infrared lamp power 500 W, wavelength 2-4 μm, irradiation distance 5 cm, substrate temperature 80℃. The thickness of the first and second interface buffer layers is 10 μm. The remaining steps are the same as in Embodiment 1.
[0178] Comparative Example 3 The difference between this comparative example and Example 1 is that no energy field is applied during the spraying of the electrolyte slurry; densification is achieved solely through solvent evaporation and subsequent hot pressing. The remaining steps are the same as in Example 1.
[0179] Comparative Example 4 The difference between this comparative example and Example 1 is that the upper and lower interface buffer layers are not sprayed; instead, the electrolyte slurry (with synchronous infrared laser assistance) is directly sprayed onto the surface of the composite positive electrode layer, and then the composite negative electrode layer is directly sprayed. The remaining steps are the same as in Example 1.
[0180] Test methods The performance, interface morphology, and interpenetration region characterization of the following embodiments and comparative examples of the present invention were all completed using the following unified testing method: Characterization of interface morphology and compositional gradient of interpenetration region The tests were performed using a focused ion beam scanning electron microscope coupled with energy dispersive spectroscopy (FIB-SEM-EDS) system, specifically a Thermo Fisher Helios 5 CX FIB-SEM.
[0181] For characterizing the compositional gradient of the interpenetrating region: Before testing, the cell cross-section was cut using FIB under argon atmosphere protection to prepare a smooth, damage-free cross-section with a thickness ≤100nm; the test parameters were: accelerating voltage 20kV, beam current 1.6nA, linear scan step size 50nm, and the test area was the interface region perpendicular to the layer thickness direction. Elemental content data were continuously collected along the layer thickness direction to obtain the distribution curve of characteristic elements along the layer thickness direction, thus determining the thickness and compositional gradient law of the interpenetrating region.
[0182] For the characterization of interface morphology and structure: the test parameters are: accelerating voltage 5kV, beam current 0.4nA, secondary electron imaging mode, to observe whether there are clear physical interfaces, pores, cracks and interlayer bonding states in the test area between adjacent layers.
[0183] Characterization of mechanical modulus gradient in interpenetrating region The nanoindentation method was used for testing with atomic force microscopy (AFM) in nanoindentation mode. The instrument was a Bruker DimensionIcon AFM. The testing environment was an argon atmosphere with a water content ≤0.1ppm and an oxygen content ≤0.1ppm. A diamond indenter was used, with a loading force of 100nN and an indentation spacing of 50nm. The test was conducted continuously along the interface direction perpendicular to the layer thickness to obtain the distribution curve of the elastic modulus along the layer thickness direction, and the modulus change rate was calculated. The critical peel load of the interface was tested using the nanoscraping method. The scratch length was 100μm, and the loading force range was 0-100mN. The minimum load at which adjacent layers peeled off was taken as the critical peel load to characterize the interlayer bonding force.
[0184] Characterization of micro-porosity in interpenetrating regions The three-dimensional reconstruction method combined with image analysis using focused ion beam scanning electron microscopy (FIB-SEM) was employed for testing. The instrument used was a Thermo Fisher Scientific Helios 5 CX FIB-SEM. Before testing, continuous FIB sections were prepared in the interpenetrating region between adjacent layers of the battery under argon atmosphere protection. The sectioning step size was 50 nm, and the number of sections was ≥50, obtaining SEM images of continuous cross-sections of the interface region. The images were aligned, denoised, and binarized using Avizo software to complete the three-dimensional reconstruction. The following were obtained: ① Average porosity of the functional layer (the central region of the functional layer away from the interface, with a test area size ≥10 μm × 10 μm × 2 μm); ② Porosity distribution curve along the layer thickness direction within the interpenetrating region; ③ Pore size distribution and pore morphology characteristics of the interface region.
[0185] Electrochemical interfacial impedance characterization Electrochemical impedance spectroscopy (EIS) was performed using an electrochemical workstation, specifically a Metrohm Autolab electrochemical workstation from Switzerland. The testing conditions were: a constant temperature environment of 25°C and a frequency range of 10 Hz.6 Hz-10 -2 Hz, AC amplitude 5mV; by fitting the equivalent circuit, the interfacial impedance between the positive electrode and the electrolyte and the interfacial impedance between the electrolyte and the negative electrode are obtained, which characterize the barrier effect of the interface on lithium-ion transport.
[0186] Battery electrochemical performance testing Charge-discharge cycle tests were conducted using the Blue Battery Testing System at a temperature of 25°C and a voltage range of 2.8V-4.2V. The first charge-discharge cycle was performed at a rate of 0.1C, and the first discharge specific capacity and first coulombic efficiency were calculated. The constant current charge-discharge cycle test was performed at a rate of 0.5C, and the capacity retention rate after 200 cycles was calculated.
[0187] Example 1: Characterization Results of Interpenetrating Regions The solid-state battery prepared in this embodiment underwent complete characterization of the interpenetration regions between the first interface buffer layer and the composite positive electrode layer, between the first interface buffer layer and the electrolyte layer, and between the second interface buffer layer and the electrolyte layer. The results are as follows: Component gradient characterization results The interface between the first interface buffer layer and the electrolyte layer was used as the core test area. EDS linear scanning tests were performed along the direction perpendicular to the layer thickness, with a total scan length of 10 μm, of which the scan length on the first interface buffer layer side was 3 μm and the scan length on the electrolyte layer side was 7 μm. The test results showed that the characteristic elements of the first interface buffer layer were F and S, and the characteristic elements of the electrolyte layer were P and S. An interpenetrating region with a thickness of 2 μm was formed in the interface region. In this interpenetrating region, the mass fraction of F element decreased linearly from 42.3 wt% on the first interface buffer layer side to 2.1 wt% on the electrolyte layer side along the layer thickness, and the mass fraction of P element increased linearly from 0 wt% on the first interface buffer layer side to 18.7 wt% on the electrolyte layer side along the layer thickness. The S element content showed a continuous linear gradient characteristic, without abrupt step changes in element content, and no obvious physical interface.
[0188] The interfaces between the composite cathode layer and the first interface buffer layer, and between the electrolyte layer and the second interface buffer layer, all form interpenetrating regions with a thickness of 1.5μm-3μm. The corresponding characteristic elements all show a continuous linear gradual change along the layer thickness direction, with no abrupt changes in content.
[0189] Mechanical modulus gradient characterization results Nanoindentation tests were performed on the interface region between the first interface buffer layer and the electrolyte layer. The results showed that the elastic modulus of the first interface buffer layer was 1.2 GPa and the elastic modulus of the electrolyte layer was 28.5 GPa. Within a 2 μm interpenetration region, the elastic modulus increased linearly from 1.2 GPa to 28.5 GPa, with a modulus change rate of 13.65 GPa / μm and no abrupt modulus step. The critical peel load of this interface was 42.3 mN, indicating excellent interlayer bonding.
[0190] The modulus of the remaining interpenetrating regions all exhibit a continuous linear gradual change along the layer thickness direction, with no abrupt changes in modulus, and the critical peel load at the interface is ≥35mN.
[0191] Interface morphology and structure characterization results FIB-SEM cross-sectional morphology observation results show that the interfaces prepared in this embodiment have no clear physical boundaries, no interface cracks or pore defects, and the particles of adjacent layers are interlocked to form a three-dimensional interlocking structure with tight interlayer bonding and no delamination.
[0192] The porosity characterization results of the interpenetration region were obtained by performing a three-dimensional reconstruction test on the interpenetration region between the first interface buffer layer and the electrolyte layer. The results showed that the average porosity of the first interface buffer layer was 4.8%, and the average porosity of the electrolyte layer was 7.9%. In the 2 μm thick interpenetration region, the porosity increased linearly from 4.8% to 7.9% along the thickness direction, with a porosity change rate of 1.55% / μm and no abrupt porosity steps. The average porosity of the interpenetration region was 6.3%, with a deviation of ≤0.2% from the arithmetic mean of the porosity of the functional layers on both sides. There were no large-size pores >200 nm in the interpenetration region, and the pores were mainly closed pores <50 nm, with no interface gaps or through pores.
[0193] The porosity of the remaining interpermeable regions exhibits a continuous linear gradient along the thickness direction, with a porosity change rate of ≤2% / μm. There are no locally high porosity regions, and the interface is densely bonded.
[0194] Electrochemical performance and interfacial impedance results EIS test results show that the interfacial impedance between the positive electrode and the electrolyte in the solid-state battery prepared in this embodiment is 80 Ω·cm. 2 The interfacial impedance between the electrolyte and the negative electrode is 45 Ω·cm. 2 The total interfacial impedance is 125 Ω·cm 2 The initial discharge specific capacity at 0.1C rate is 190mAh / g, and the initial coulombic efficiency is 84%. After 200 cycles at 0.5C rate, the discharge specific capacity retention rate is 94%, and there is no significant increase in interface impedance during cycling.
[0195] Comparative Example 1: Interface Characterization Comparison Results This comparative example uses the exact same material system as Example 1, but employs a conventional blade coating and stacking process to form an electrolyte film with a thickness of approximately 200 μm. The interface characterization results are as follows: Composition gradient characterization results show that the content of characteristic elements in the corresponding interface region changes abruptly in the range of <100nm, with no continuous transition region, a clear physical interface, and no interpenetrating region. The mechanical modulus characterization results show that the elastic modulus of the interface region abruptly changes from 1.1 GPa to 29.2 GPa in the < 100 nm range, with a modulus abrupt change rate of 281 GPa / μm, indicating a severe modulus mismatch; the critical peel load at the interface is only 12.7 mN, indicating extremely poor interlayer bonding. The interface morphology observation results show that there is a clear physical interface in the interface region, with gaps and pores of 50nm-200nm at the interface. The interlayer is only in physical contact and there is no interlocking structure. The results of the interfacial micro-region porosity characterization were obtained by testing the corresponding interfacial regions. The results showed that the average porosity of the first interfacial buffer layer was 5.1%, and the average porosity of the electrolyte layer was 19.8%. The porosity of the interfacial region changed abruptly from 5.1% to 28.7% in the <100nm range, with the highest porosity reaching 42% at the interfacial seams. The porosity change rate was >2360% / μm, and there was no continuous gradual change. There were a large number of 200nm-1μm gaps and through-pores at the interface, indicating loose interlayer contact and a clear physical interface.
[0196] Electrochemical test results show that the interfacial impedance between the positive electrode and the electrolyte in the battery prepared in this comparative example is 200 Ω·cm. 2 The interfacial impedance between the electrolyte and the negative electrode is 135 Ω·cm. 2 The total interfacial impedance is 335 Ω·cm 2 The initial discharge specific capacity at 0.1C rate is 175mAh / g, and the initial coulombic efficiency is 80%. After 200 cycles at 0.5C rate, the capacity retention is only 88%, and a sudden increase in interface impedance occurs after 100 cycles.
[0197] Compared with the prior art, the present invention has the following significant technical effects: This invention, through the assistance of an energy field applied synchronously during the spraying process, constructs an interpenetrating region with continuously linearly varying composition and modulus between adjacent functional layers, completely eliminating the modulus abrupt change and stress concentration at the rigid interface in the traditional multilayer stacking process, reducing the interfacial impedance between the positive electrode and the electrolyte by more than 60%, and fundamentally solving the core problem of poor solid-solid interface contact and easy separation during cycling in solid-state batteries. The three-dimensional interlocking structure of the interpenetrating region increases the critical peel load between layers by more than 2 times, greatly enhancing the bonding stability of the multilayer structure. During charging and discharging, it can adapt to the volume change of the electrode material and continuously maintain tight contact at the interface, so that the capacity retention rate of the battery can reach more than 94% after 200 cycles at 0.5C rate. Synchronous energy field assistance enables in-situ densification of the electrolyte layer, achieving a density of over 92%, forming a continuous ion transport channel, significantly improving ion conductivity. Simultaneously, in conjunction with the continuous ion transport path in the interpenetration region, it further reduces the overall impedance of the battery, improving the rate performance and energy density of the battery.
[0198] The electrochemical performance of the NCM811 sulfide electrolyte silicon-carbon full cells prepared in Example 1 and Comparative Example 1 was tested. (See attached text.) Figure 4 The test results showed that the interfacial impedance between the positive electrode and the electrolyte of the battery in Example 1 before cycling was approximately 80 Ω·cm when fitted by electrochemical AC impedance spectroscopy. 2 The interfacial impedance of the comparative example 1 battery is approximately 200 Ω·cm. 2 At a 0.1C rate, the initial discharge specific capacity of the battery in Example 1 was 190 mAh / g, and the initial coulombic efficiency was 84%; the initial discharge specific capacity of the battery in Comparative Example 1 was 175 mAh / g, and the initial coulombic efficiency was 80%. After 200 cycles at a 0.5C rate, the capacity retention of the battery in Example 1 was 94%, and the capacity retention of the battery in Comparative Example 1 was 88%.
[0199] The lithium-rich manganese-based cathode composite electrolyte silicon-carbon full cells prepared in Example 2 and Comparative Example 2 were subjected to electrochemical performance tests. The test results showed that the cathode-electrolyte interfacial impedance of the battery in Example 2 before cycling was approximately 100 Ω·cm. 2 The interfacial impedance of the comparative example 2 battery is approximately 300 Ω·cm. 2 At a 0.1C rate, the initial discharge specific capacity of the battery in Example 2 was 200 mAh / g, and the initial coulombic efficiency was 88%; the initial discharge specific capacity of the battery in Comparative Example 2 was 185 mAh / g, and the initial coulombic efficiency was 84%. After 200 cycles at a 0.5C rate, the capacity retention of the battery in Example 2 was 90%, and the capacity retention of the battery in Comparative Example 2 was 85%.
[0200] Comparative Example 1 (with infrared laser) and Comparative Example 3 (without energy field assistance): Density: 92% vs 85%; Ionic conductivity: 1.98 vs 1.47 mS / cm; Energy field assistance improves the surface contact of electrolyte particles by instantaneous heating, significantly enhancing the film density and ion transport capacity, which is one of the core technical features of this invention.
[0201] The test results of Examples 1-6 and Comparative Examples 1-4 are shown in Tables 1 and 2 below: Table 1: Table 2: It should be noted that the testing methods and meanings of each parameter in the table above are as follows: The bulk porosity of the electrolyte layer is calculated from the electrolyte layer density. The specific relationship is: bulk porosity of electrolyte layer = 100% - electrolyte layer density. The test area is limited to the central region inside the electrolyte layer away from each interface. The size of the test area is ≥10μm×10μm×2μm, so as to eliminate the interference of the interface transition region on the test results.
[0202] The average thickness of the interpenetrating region was obtained through FIB-SEM-EDS line scan testing. Specifically, it is defined as the thickness of the region in which the content of characteristic elements shows a continuous linear gradient along the thickness direction. For samples that do not show a continuous gradient, this indicator is marked with "-", indicating that there is no interpenetrating region that meets this definition.
[0203] In samples with interpenetrating regions, the porosity change rate refers to the change in porosity per unit length along the stacking direction within the interpenetrating region. For samples without interpenetrating regions, this indicator refers to the magnitude of the porosity jump within a narrow space in the interface abrupt change region. This allows for a direct distinction between the essential differences in pore structure evolution characteristics between gradually changing interpenetrating regions and traditional abrupt interfaces.
[0204] The critical peel load of the interface was tested using the nano-scratching method. It was defined as the minimum applied load corresponding to the interlayer peeling that occurs at the interface. The higher the value, the stronger the interlayer bonding force between adjacent functional layers.
[0205] In Examples 1 to 6, the average porosity P of the interpenetrating regions all satisfy the relationship defined in the claims of this application, namely... Where P1 is the bulk average porosity of the interface buffer layer, with a stable test value of 4.5%-5.0%, and P2 is the corresponding bulk porosity of the electrolyte layer.
[0206] The test results above show that the technical solution of the present invention has made significant progress in terms of reducing interface impedance, increasing energy density, and improving cycle stability, providing a practical and feasible technical path for the large-scale preparation of high-energy-density and high-safety all-solid-state batteries.
[0207] The present invention has been described in detail above.
Claims
1. A solid-state battery, characterized in that, It includes a current collector, a composite positive electrode layer, an electrolyte layer and a composite negative electrode layer arranged sequentially in the stacking direction; The solid-state battery further includes at least one interface buffer layer, which is disposed between the composite positive electrode layer and the electrolyte layer, and / or between the electrolyte layer and the composite negative electrode layer; At least one of the interface buffer layers extends into each other with at least one adjacent layer. The mutually extending portions constitute an interpenetrating region, and the thickness of the interpenetrating region along the stacking direction is 0.5μm-5μm.
2. The solid-state battery according to claim 1, characterized in that, Within the interpenetrating region, the chemical composition of the material changes continuously and gradually along the stacking direction.
3. The solid-state battery as described in claim 1, characterized in that, At least one of the interface buffer layers includes a first interface buffer layer and a second interface buffer layer; the first interface buffer layer is disposed between the composite positive electrode layer and the electrolyte layer, and the second interface buffer layer is disposed between the electrolyte layer and the composite negative electrode layer.
4. The solid-state battery as described in claim 3, characterized in that, Interpenetration regions are formed between the first interface buffer layer and the composite positive electrode layer, between the first interface buffer layer and the electrolyte layer, between the second interface buffer layer and the electrolyte layer, and between the second interface buffer layer and the composite negative electrode layer.
5. The solid-state battery as described in claim 1, characterized in that, Within the interpenetrating region, the porosity exhibits a continuous linear gradual change along the layer thickness direction, without any abrupt changes in porosity.
6. The solid-state battery as described in claim 5, characterized in that, Within the interpenetrating region, the porosity variation rate along the layer thickness direction is ≤5% / μm.
7. The solid-state battery as described in claim 5, characterized in that, The average porosity P of the interpenetrating region satisfies the following relationship: in, The average porosity of the first functional layer corresponding to the interpenetrating region is the bulk average porosity. The average porosity of the second functional layer corresponding to the interpenetrating region is the average porosity of the central region of the functional layer away from the interpenetrating region.
8. A method for preparing a solid-state battery, characterized in that, Includes the following steps: A composite positive electrode layer is formed on the current collector; An electrolyte layer, at least one interface buffer layer, and a composite negative electrode layer are formed on the side of the composite positive electrode layer away from the current collector, such that at least one of the interface buffer layers is located between the composite positive electrode layer and the electrolyte layer, and / or between the electrolyte layer and the composite negative electrode layer; After further processing, a solid-state battery is obtained; During the formation of at least one of the interface buffer layer, the electrolyte layer, and the composite negative electrode layer, an energy field is simultaneously applied to assist in the formation of the interface buffer layer and its adjacent at least one layer, thereby forming an interpenetrating region.
9. The method for preparing a solid-state battery as described in claim 8, characterized in that, The interface buffer layer includes a first interface buffer layer and a second interface buffer layer; the step of forming an electrolyte layer, at least one interface buffer layer, and a composite negative electrode layer on the side of the composite positive electrode layer away from the current collector includes: The first interface buffer layer is formed on the composite positive electrode layer; The electrolyte layer is formed on the first interface buffer layer by spraying. The second interface buffer layer is formed on the electrolyte layer by spraying. The composite negative electrode layer is formed on the second interface buffer layer; Furthermore, an energy field is applied simultaneously during the formation of the first interface buffer layer, the electrolyte layer, the second interface buffer layer, and the composite negative electrode layer.
10. The method for preparing a solid-state battery as described in claim 8, characterized in that, The energy field assistance includes at least one of low-intensity pulsed laser scanning, focused infrared radiation, or pulsed hot air assistance.
11. The method for preparing a solid-state battery as described in claim 8, characterized in that, The energy field-assisted application parameters are: power density 0.1 W / mm². 2 Up to 1W / mm 2 The area of action moves synchronously with the area of spraying.
12. The method for preparing a solid-state battery as described in claim 10, characterized in that, When the energy field assistance includes focused infrared radiation, the wavelength of the focused infrared radiation is 2μm to 5μm, the diameter of the irradiated area is 1mm to 3mm, and the focused infrared radiation causes the surface of the irradiated particles to be instantly heated to 150°C to 200°C.
13. The method for preparing a solid-state battery as described in claim 8, characterized in that, The steps for forming a composite cathode layer on the current collector include: A positive electrode active material, a first conductive agent, a first ionic conductor additive, and a binder are dispersed in a solvent to prepare a positive electrode slurry. The positive electrode slurry is deposited on the surface of the current collector by ultrasonic spraying. After spraying, it is dried in a vacuum environment at 80°C for 12 hours.
14. The method for preparing a solid-state battery as described in claim 13, characterized in that, In the positive electrode slurry, the mass ratio of the positive electrode active material, the first ion conductor additive, the first conductive agent and the binder is (60-90):(5-35):(1-5):(1-5).
15. The method for preparing a solid-state battery as described in claim 13, characterized in that, The positive electrode active material includes at least one of lithium cobalt oxide, nickel-cobalt-manganese ternary cathode, and sulfur composite cathode. The first ionic conductor additive includes at least one of the following: silver sulfide electrolyte, thio-LISICON type electrolyte, LGPS type electrolyte, glassy sulfide electrolyte, glass ceramic type electrolyte, or halogen-doped derivatives of any of the foregoing. The first conductive agent is any one or more of the following: particulate conductive agent, fibrous conductive agent, flake conductive agent, or a first composite conductive agent composed of at least two of the aforementioned conductive agents.
16. The method for preparing a solid-state battery as described in claim 15, characterized in that, The particulate conductive agent includes at least one of acetylene black, Ketjen black, Super P, and conductive carbon black.
17. The method for preparing a solid-state battery as described in claim 15, characterized in that, The fibrous conductive agent includes at least one of vapor-grown carbon fiber, single-walled carbon nanotube, multi-walled carbon nanotube, and carbon fiber.
18. The method for preparing a solid-state battery as described in claim 15, characterized in that, The sheet-like conductive agent includes at least one of graphene, conductive graphite, and expanded graphite.
19. The method for preparing a solid-state battery as described in claim 15, characterized in that, The first composite conductive agent includes at least one of a composite of carbon nanotubes and carbon black, a composite of graphene and carbon black, or a composite of carbon nanotubes and graphene.
20. The method for preparing a solid-state battery as described in claim 13, characterized in that, The solid content of the positive electrode slurry is 40% to 65%.
21. The method for preparing a solid-state battery as described in claim 13, characterized in that, The solid content of the positive electrode slurry is 50% to 55%.
22. The method for preparing a solid-state battery as described in claim 9, characterized in that, The step of forming the first interface buffer layer on the composite positive electrode layer includes: A polymer matrix and lithium salt are dissolved in a solvent to prepare an interface buffer layer slurry, which is then deposited onto the surface of the composite positive electrode layer using ultrasonic spraying.
23. The method for preparing a solid-state battery as described in claim 9, characterized in that, The step of forming the electrolyte layer on the first interface buffer layer by spraying includes: Solid electrolyte material and binder are dispersed in a solvent to form an electrolyte slurry, which is then deposited on the surface of the first interface buffer layer using ultrasonic spraying.
24. The method for preparing a solid-state battery as described in claim 23, characterized in that, The mass ratio of the solid electrolyte material to the binder is (90-99.9):(0.1-10).
25. The method for preparing a solid-state battery as described in claim 23, characterized in that, The solid electrolyte material includes at least one of sulfide solid electrolyte, oxide solid electrolyte, polymer solid electrolyte, or halide solid electrolyte.
26. The method for preparing a solid-state battery as described in claim 23, characterized in that, The solid content of the electrolyte slurry is 40-70%.
27. The method for preparing a solid-state battery as described in claim 9, characterized in that, The step of forming the second interface buffer layer on the electrolyte layer by spraying includes: A polymer matrix and lithium salt are dissolved in a solvent to prepare an interface buffer layer slurry, which is then deposited onto the surface of the electrolyte layer using ultrasonic spraying.
28. The method for preparing a solid-state battery as described in claim 22 or 27, characterized in that, The polymer matrix includes at least one of polyvinylidene fluoride-hexafluoropropylene, polyoxyethylene, or polypropylene carbonate.
29. The method for preparing a solid-state battery as described in claim 22 or 27, characterized in that, The lithium salt includes at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium bis(pentafluoroethylsulfonyl)imide, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium perchlorate, lithium bis(oxalateborate), lithium difluorooxalateborate, lithium tetrafluorooxalate phosphate, and lithium trifluoromethanesulfonate.
30. The method for preparing a solid-state battery as described in claim 22 or 27, characterized in that, The amount of lithium salt added is 0.1-5% of the total mass of the interface buffer layer slurry.
31. The method for preparing a solid-state battery as described in claim 9, characterized in that, The step of forming the composite negative electrode layer on the second interface buffer layer includes: A negative electrode slurry is prepared by dispersing the negative electrode active material, the second ion conductor additive, the second conductive agent and the binder in a solvent. The negative electrode slurry is deposited on the surface of the second interface buffer layer by ultrasonic spraying, and an energy field is applied simultaneously during the process of spraying to form the composite negative electrode layer.
32. The method for preparing a solid-state battery as described in claim 31, characterized in that, In the negative electrode slurry, the mass ratio of negative electrode active material, second ion conductor additive, second conductive agent and binder is (60-85):(10-30):(1-5):(1-5).
33. The method for preparing a solid-state battery as described in claim 31, characterized in that, The negative electrode active material is any one or more of the following materials: silicon, silicon-carbon composite material, silicon suboxide, graphite, lithium metal, tin, aluminum, antimony, titanium dioxide, lithium titanate, or a composite material formed from at least two of the aforementioned materials; The second ion conductor additive includes at least one of the following: sulfide solid electrolyte, oxide solid electrolyte, halide solid electrolyte, polymer solid electrolyte, and composite solid electrolyte; The second conductive agent is any one or more of the following: carbon black conductive agent, carbon fiber conductive agent, carbon sheet conductive agent, metal conductive agent, or a second composite conductive agent composed of at least two of the aforementioned conductive agents.
34. The method for preparing a solid-state battery as described in claim 31, characterized in that, When an energy field is simultaneously applied during the spraying process to form the composite negative electrode layer, the energy field assistance used is low-intensity pulsed laser scanning. The wavelength of the low-intensity pulsed laser scanning is 800-1200 nm, the pulse width is 10 ns-100 ms, and the energy density is 0.1-10 J / cm³. 2 .
35. The method for preparing a solid-state battery according to any one of claims 13, 23, or 31, characterized in that, The adhesive is any one or more of the following: polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid, polyisobutylene, styrene-ethylene-butene-styrene block copolymer, polyamide-imide, polyvinyl alcohol, polyethylene oxide, or a composite adhesive composed of at least two of the foregoing.
36. The method for preparing a solid-state battery according to any one of claims 13, 22, 23, 27 or 31, characterized in that, The solvent includes at least one of N-methylpyrrolidone, acetone, n-heptane, acetonitrile, tetrahydrofuran, toluene, xylene, isobutyl isobutyrate, or cyclohexane.
37. The method for preparing a solid-state battery according to any one of claims 13, 22, 23, 27 or 31, characterized in that, When forming each layer using ultrasonic spraying, the spraying parameters are: atomization frequency of 20kHz to 200kHz, carrier gas pressure of 0.1MPa to 0.5MPa, spraying rate of 1mL / min to 100mL / min, substrate temperature of the current collector of 25℃ to 120℃, and spraying distance of 5cm to 30cm.
38. The method for preparing a solid-state battery as described in claim 8, characterized in that, After subsequent processing, the solid-state battery obtained includes: The resulting multilayer structure is vacuum dried at 60-120℃ for 6-24 hours, then rolled under 20-80MPa pressure, and then punched, stacked, and packaged to obtain a solid-state battery.
39. The method for preparing a solid-state battery as described in claim 9, characterized in that, The thickness of the composite positive electrode layer and the composite negative electrode layer is 20 μm to 500 μm, the thickness of the electrolyte layer is 5 μm to 100 μm, and the thickness of the first interface buffer layer and the second interface buffer layer are each independently 0.1 μm to 10 μm.
40. A solid-state battery fabrication system, characterized in that, The system for implementing the method for preparing a solid-state battery according to any one of claims 8 to 39 comprises: At least four independently controlled ultrasonic atomizing nozzles, each of which is used to atomize and spray the slurry onto the surface of the current collector or the surface of the layer structure already formed on the current collector; The slurry delivery unit is connected to each of the ultrasonic atomizing nozzles and is used to supply slurry to each of the ultrasonic atomizing nozzles. An energy field auxiliary generator, the area of which moves synchronously with the spraying area of the ultrasonic atomizing nozzle, is used to apply an energy field during the spraying process; A temperature-controlled moving platform is used to carry and heat the collector fluid, and to move the collector fluid relative to the ultrasonic atomizing nozzle; and The computer program control system is electrically connected to the ultrasonic atomizing nozzle, the slurry delivery unit, the energy field auxiliary generator, and the temperature-controlled moving platform, and is used to control the spraying path, spraying parameters, energy field parameters, and platform temperature and moving speed.